Phosphocreatine mitigates pulmonary fibrosis in STZ-induced diabetic rats with bleomycin injury through TGF-β/Smad and Wnt/β-catenin pathways - Fu Han Wang; Abdulrahman Khaled Alwesabi; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Marwan almoiliqy (Tissue and Cell, 2027)

Void fraction intermittency and its role in two-phase fluidelastic instability in nuclear steam generators - Hossein Farani Sani; Amro Elhelaly; Marwan Hassan; Atef Mohany (Annals of Nuclear Energy, 2026)

Post-glacial landforms dictate fluvial sediment dynamics during extreme floods: Morphological adjustments and flood hazard implications - David Puhl; Marwan A. Hassan (Geomorphology, 2026)

From local suitability to global applicability: An integrated experimental-numerical investigation of climate-responsive hygrothermal performance of a novel straw bale wall - Marwan Assaf; Franck Brachelet; Pierre Tittelein; Didier Defer; Emmanuel Antczak (Energy and Buildings, 2026)

Artificial photosynthesis of H2O2 with covalent organic frameworks: From structural design to catalytic function - Ajmal Khan; Yasser A. Alassmy; Mohammed Qasem Alfaifi; Marwan M. Abduljawad; Sultan A. Alshuhri; Irshad Ahmad; Qinyun Huang; Yuyu Liu; Muhammad Arshad (Journal of Environmental Chemical Engineering, 2026)

Reconciling technical compliance with lived experience: applying a mixed-methods approach to evaluate occupant satisfaction in a high-performance educational building - Abdurrahman Baru; Qinghao Zeng; Marwan Shagar; Tran Duong Nguyen; Pardis Pishdad; Eunhwa Yang (Building and Environment, 2026)

Detection of Natural Killer and Natural Killer T Cells Responses among Patients with Chronic Hepatitis C Infections in Sana’a City-Yemen - Ahmed M. Abdulkareem; Basheer A. Al-Ofairi; Mansour Ali Al-Amrani; Marwan K. Saeed; Majed A. Al-Jahrani; Wadhah Hassan Edrees; Shiburaj Sugathan; Ansam Wadia Al-shameri; Ammar AL-Farga (Current Microbiology, 2026)

Hydro-chemical variations of spring water quality in Matwi catchment – Salfeet / Palestine - Marwan Ghanem; Wasim Ahmad; Holger Schuttrumpf; Rawan Mlih; Ghaleb Natour (Arabian Journal of Geosciences, 2026)

Phosphocreatine attenuates diabetes-exacerbated kidney fibrosis via TGF-β/Smad and PI3K/Akt pathways in a dual rat model - Fu Han Wang; Abdulrahman Khaled Alwesabi; Wu Liu; Mueataz A. Mahyoub; Marwan almoiliqy; Eskandar Qaed; Waleed Aldahmash (Tissue and Cell, 2026)

District-level healthcare accessibility under flood-conditioned road network disruption in Pakistan - Ramla Khan; Martin Lauer; Muhammad Marwan (Spatial Information Research, 2026)

Modeling seawater intrusion with multiple sources of uncertainty: Application to Kuwait City - Bashayer Alshammari; Rashad Abbasov; Anis Younes; Husam Musa Baalousha; Renaud Toussaint; Jean-Christophe Comte; Marwan Fahs (Hydrogeology Journal, 2026)

Impact of carvedilol versus metoprolol on ventricular arrhythmia burden and ICD therapies: a systematic review and meta-analysis - Ahmed E. Ali; Marwan H. Ahmed; Karim Ali; Mostafa Ali; Mohamed K.A. Awad (European Journal of Clinical Pharmacology, 2026)

Uncontrolled husbandry variability biases behavioral, endocrine, and molecular outcomes in zebrafish - Hussein M.K. Al-Mohammad; Hanan Shihab Ahmad; Dohoa Kadhium Alshamarey; Ahmed Jabbar Obaid; Marwan Abdulrazzaq Kamil; Amjed Abdulabbas Sayah Gaffl Alibraheemi (Applied Animal Behaviour Science, 2026)

Denning Phenology Mediates Sea‐Ice Loss Impacts on Early Reproductive Success in Polar Bears - Marwan Naciri; Jon Aars; Marlène Gamelon; Magnus Andersen; Andrew E. Derocher; Øystein Wiig; Sarah Cubaynes (Global Change Biology, 2026)
Climate change is disrupting myriad biological processes, including the ability of species to synchronize life‐history events with optimal environmental conditions, with potential fitness impacts. Changes in migratory and breeding phenology and their consequences on fitness have been well studied in birds and some mammals. By contrast, changes in the phenology of overwinter sheltering and their influence on fitness have rarely been investigated. Pregnant female polar bears ( Ursus maritimus ) spend the winter fasting in a maternity den where they give birth and nurse their cubs until emergence in early spring. To sustain their fast, females rely on energy stores built primarily through consumption of ice‐associated seals. Here, we assess the impact of sea‐ice loss driven by climate change on early reproductive success acting through disrupted denning phenology and other unspecified factors. To do so, we develop a Bayesian hierarchical model combining capture–recapture and path modeling. We apply it to 38 years of capture–recapture data along with biologging data on denning status and phenology, while accounting for imperfect detection and uncertainty in individual denning schedules. We found that low sea‐ice availability led to earlier den emergence, which in turn reduced early litter survival and possibly litter size. By contrast, there was little evidence that sea‐ice availability affected early reproductive success through pathways independent of denning phenology (e.g., litter mass). Considering both direct and indirect effects, low sea‐ice availability reduced early litter survival but not the size of surviving litters. Given the strong link between sea‐ice conditions and body condition in female polar bears, we conclude that sea‐ice loss exerts an energetic constraint on denning females, forcing them to depart from dens early, which jeopardizes their cubs, ultimately reducing maternal fitness. Similar impacts of climate change may occur in other species where phenology is determined by body condition.

Desertification assessment in the Wadi Al-Nar Watershed, West Bank, Palestine - Omar Mehisen; Marwan Ghanem (Mediterranean Geoscience Reviews, 2026)

Oscillation-induced synchronization hubs in global hydrological extremes - Jianxin Zhang; Kai Liu; Yunhui Sui; Kaiwen Li; Lianjie Qin; Junfei Liu; Ming Wang; Norbert Marwan (Journal of Hydrology, 2026)

Control strategies for solar direct drive refrigerators to achieve off-grid cold storage - Marwan Abugabbara; Jonas Kjær Jensen; Ivan Katic (International Journal of Refrigeration, 2026)

Multi-step Daily Reservoir Inflow Prediction using Temporal Conventional Network Model Integrating time-Varying Filter-Based empirical mode Decomposition and Holt-Winters Algorithms - Atefeh Sadat Hosseini; Sultan K. Salamah; Ahmed Alkhayyat; Anupam Yadav; Abhinav Kumar; Marwan Kheimi; Sandeep Singh; KDV Prasad (Water Resources Management, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Making waves: the perpetual membrane - Abedalkader Alkhouzaam; Marwan Khraisheh (Water Research, 2026)

Field-realistic accelerated aging protocol for spiral-wound reverse osmosis membranes: multi-scale diagnostics and end-of-life criteria - Abedalkader Alkhouzaam; Marwan Khraisheh (Desalination, 2026)

Nanoformulated Quetiapine for Enhanced Therapeutic Efficacy in vivo Studies: a Systematic Review and Meta-Analysis - Öznur Özge Özcan; Burcu Çevreli; Belkıs Atasever-Arslan; Marwan Abdelmahmoud Abdelkarim Maki; Palanirajan Vijayaraj Kumar; Türker Tekin Ergüzel (Journal of Pharmaceutical Innovation, 2026)
Objectives Quetiapine exhibits low oral bioavailability and limited blood–brain barrier (BBB) penetration, restricting its therapeutic efficacy in central nervous system (CNS) disorders. This systematic review and meta-analysis examined whether nanoparticle-based delivery systems improve systemic exposure, brain targeting, and functional outcomes in rodent models of schizophrenia. Plasma Cmax was the only harmonized outcome eligible for quantitative pooling, whereas Brain Cmax was synthesized descriptively due to inconsistent reporting. Methods Following PRISMA 2020 guidelines, five databases were searched through June 2025. Seventeen in vivo studies met eligibility criteria. Six provided harmonized Plasma Cmax data (ng/mL, mean ± SD) suitable for quantitative pooling using random-effects models. All other pharmacokinetic outcomes—including Brain Cmax, brain AUC, bioavailability, and brain/plasma ratios—were synthesized descriptively due to inconsistent reporting. A REML-based meta-regression evaluated whether administration route (oral, intranasal, intravenous) moderated Plasma Cmax effect sizes. Risk of bias was assessed using SYRCLE, and certainty of evidence with GRADE. Results Across studies, nanoformulations such as solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC), albumin nanoparticles, intranasal microemulsions, and lipid-core nanocapsules consistently enhanced systemic and central exposure compared with conventional quetiapine. Meta-analysis showed a large, significant improvement in Plasma Cmax (SMD = 6.93; 95% CI: 3.41–10.45; p < 0.001), despite high heterogeneity (I 2 = 96.1%). Meta-regression indicated that route of administration explained ~ 21% of between-study variance but did not significantly affect effect size ( p = 0.281). Descriptive synthesis demonstrated consistent increases in Brain Cmax, brain AUC, early brain uptake, and brain/plasma ratios, particularly for lipid-based and intranasal nanosystems. Behavioral findings (improved PPI, reduced immobility, normalized locomotion) aligned with enhanced CNS exposure. GRADE rated Plasma Cmax as moderate certainty; all other outcomes were low to very low due to methodological variability and small sample sizes. Conclusion Nanoformulated quetiapine markedly improves pharmacokinetic performance in preclinical schizophrenia models, with strong and consistent gains in both systemic exposure and CNS targeting. Lipid-based and intranasal nanoformulations show the greatest promise for enhancing brain delivery. Standardized reporting of brain PK metrics (especially Brain Cmax and AUC), harmonized sampling schedules, and rigorously powered designs will be essential for future translational advancement of nano-enabled quetiapine.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Integrating ensemble and contrastive learning with explainable AI for modeling eutrophication-driven algal risks - Sultan K. Salamah; Marwan Kheimi; Mohammad Zounemat-Kermani (Environmental Monitoring and Assessment, 2026)

High predictability potential of highly synchronized widespread floods in monsoon regions - Jianxin Zhang; Kai Liu; Ming Wang; Kaiwen Li; Fenying Cai; Josef Ludescher; Jürgen Kurths; Norbert Marwan (Journal of Hydrology, 2026)

Contribution and applications of demographic concepts to conservation - Christie Le Coeur; Jan Perret; Aurélien Besnard; Sarah Cubaynes; Célian Monchy; Marwan Naciri; Mónia Nakamura; Olivier Gimenez (Biological Conservation, 2026)

Elucidating the Dual Role of Colchicine in Zinc Oxide Nanoparticle Synthesis: A Box–Behnken Design Approach with Structural, Computational, and Antibacterial Evaluation - Ashok Kumar Janakiraman; Tan Qinwei; Jamal Moideen Muthu Mohamed; Ramkanth Sundarapandian; Marwan Abdelmahmoud Abdelkarim Maki; M. Yasmin Begum; Wong Pui Ling; Saminathan Kayarohanam; T.S. Mohamed Saleem (Journal of Pharmaceutical Innovation, 2026)

Diverse methods of incorporating physics into neural networks: A comprehensive review - Mohammad Mahdi Rajabi; Marwan Fahs; Maryam Mansouri Bajgiran; Anis Younes; François Lehmann (Journal of Hydrology, 2026)

Potential links between the North Atlantic oscillation and Arctic Oscillation on spring rainfall in Iraq - Ahmad Majid Abbas; Mohammed Younus jabbar; Eman Hussein Rahsid; Mawj Diya Hussain; Marwan Abdullah Mohammad; Noora Zayid Atti; Hussein Majid Abbas (Theoretical and Applied Climatology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Phosphocreatine attenuates doxorubicin-induced hepatotoxicity via activation of Nrf2/HO-1 and PGC-1α pathways in mice - Eskandar Qaed; Mueataz A. Mahyoub; Waleed Q.A. Naji; Fu Han Wang; Wu Liu; Waleed Aldahmash; Zeyao Tang; Marwan almoiliqy (Tissue and Cell, 2026)

How operational strategies influence nitrogen removal and nitrous oxide emissions: Insights from a full-scale wastewater treatment plant - Mostafa Khalil; Marwan Alsaleh; Ahmed Elsayed; Hussein Aqeel; Ahmed Al-Omari; Shannon Cavanaugh; Farokh Laqa Kakar; Katherine Bell; Allegra K. da Silva; Jose Porro; Ahmed AlSayed; Steven N. Liss; et al. (Journal of Environmental Management, 2026)

Evaluating boiling point elevation impacts on design accuracy and economic viability of high-recovery multi-effect desalination - Husam Zawati; Sattam Alharbi; Mohamed A. Abdelatief; Marwan Hameed; Mohamed Abdelkareem (Desalination, 2026)

Spatiotemporal dynamics of moisture influx and their role in precipitation extremes: A study of December 2023 in Kayalpattinam - Sree Anusha Ganapathiraju; Utkarsh Kanth; Madhuri Sai Latha V.; Maheswaran Rathinasamy; Niranjan Kumar Kondapalli; Sara M. Vallejo-Bernal; Norbert Marwan; Sukhwinder Kaur (Atmospheric Research, 2026)

Inter-comparison of medium-resolution satellite albedo retrieval techniques over snow and ice - Pablo Fuchs; Heather Purdie; Brian Anderson; Shelley MacDonell; Ruzica Dadic; Marwan Katurji (International Journal of Remote Sensing, 2026)

Explainable Artificial Intelligence in Hydrology: A Review - Mohammad Zounemat-Kermani; Marwan Kheimi (Water Resources Management, 2026)

The MicroRNAs-STAT3-cyclophilin D-cell apoptosis axis: a novel pathway for phosphocreatine treatment in heart disease - Eskandar Qaed; Wu Liu; Marwan Almoiliqy; Waleed Aldahmash; Mueataz A. Mahyoub; Haya A. Elshafei; Zeyao Tang (Journal of Molecular Histology, 2026)

From waste to value: microbial valorization of low-cost renewable resources for hyaluronic acid production - Ehab Marwan-Abdelbaset; XiaoYun Lu; Mohamed Samy-Kamal; Dan Tan (Waste Management, 2026)

Assessing simplified approaches in modeling rainfall-induced landslides using Richards' equation with Biot poroelasticity - Rashad Abbasov; Marwan Fahs; Vincent Fontaine; Husam Musa Baalousha; Anis Younes; Renaud Toussaint (Engineering Geology, 2026)

Can through-water Structure-from-Motion photogrammetry characterize topographic statistics of gravel-bed surfaces? - Chendi Zhang; Wenqi Li; Marwan A. Hassan (Geomorphology, 2025)

Interpretable ensemble learning for modeling phosphorus dynamics and mitigating eutrophication in riverine ecosystems - Marwan Kheimi; Mohammad Zounemat-Kermani (Ecohydrology & Hydrobiology, 2025)

Therapeutic efficacy of baicalein and 6-(methylsulfinyl)hexyl isothiocyanate, alone or in combination with 5-fluorouracil, in the treatment of colorectal cancer - Janset S. Anzour; Mona A. Khamis; Marwan Emara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Fungal peritonitis in peritoneal dialysis patients: a nationwide cohort study - Margarita Kunin; Tatiana Tanasiychuk; Nabil Abu-Amer; Hila Soetendorp; Yael Einbinder; Sharon Mini; Alon Bnaya; Yael Kenig-Kozlovsky; Yael Golomb; Regina Gershkovitz; Roza Rosenberg; Netta Lev; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Stage–discharge relationships in vegetated channels with overbank floods - Hongsheng Fu; Yuqi Shan; Marwan A. Hassan; Kejun Yang; Chao Liu (Journal of Hydrology, 2025)

Phosphocreatine alleviates liver fibrosis in diabetic mice by targeting TGF-β/Smad and α-SMA pathways - Fu Han Wang; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Dalal Sanad Al-Mutairi; Zeyao Tang; Marwan almoiliqy (Tissue and Cell, 2025)

Systematic review of residential indoor environmental quality assessment surveys and the development of an exemplary novel survey identifying and analyzing tool - Marwan Shagar; Qinghao Zeng; Abdurrahman Baru; Eunhwa Yang; Pardis Pishdad (Building and Environment, 2025)

Introducing institutional design principles for transforming on-ground biosecurity - Yiheyis T. Maru; Heleen Kruger; Barton Loechel; Marta Hernandez-Jover; Jennifer Kelly; Jennifer Manyweathers; Marwan El Hassan (Agricultural Systems, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Sketching a Space of Brain States - Maria Mannone; Patrizia Ribino; Peppino Fazio; Norbert Marwan (Neuroinformatics, 2025)
Brain functional connectivity alterations, that is, pathological changes in the signal exchange between areas of the brain, are occurring in several neurological diseases, including neurodegenerative and neuropsychiatric ones. They consist in changes in how brain functional networks work. By conceptualising a brain space as a space whose points are connectome configurations representing brain functional states, changes in brain network functionality can be represented by paths between these points. Paths from a healthy state to a diseased one, or between diseased states as instances of disease progression, are modelled as the action of the Krankheit-Operator , that produces changes from a brain functional state to another one. This study proposes a formal representation of the space of brain states and presents its computational definition. Moreover, references to patients affected by Parkinson’s disease, schizophrenia, and Alzheimer-Perusini’s disease are included for discussing the proposed approach and possible developments of the research toward a generalisation.

Conventional and advanced AI-based models in soil moisture prediction - Marwan Kheimi; Mohammad Zounemat-Kermani (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

The agrifood-system wage gap and structural transformation: cross-country evidence - Marwan Benali; Vanya Slavchevska; Natalia Piedrahita; Benjamin Davis; Nicholas Sitko; Carlo Azzarri; Gianluigi Nico; Dung Thi Le; Jessika Kluth (Global Food Security, 2025)

A robust Mixed Finite Element model for coupled Thermo-Hydro-Mechanical problems in unsaturated porous media - Lingai Guo; Anis Younes; Marwan Fahs; Hussein Hoteit (Computers and Geotechnics, 2025)

Advanced bioimpedance analysis for infectious disease risk assessment via neural network classifiers - Sergey Filist; Riad Taha Al-Kasasbeh; Tigran Gagikovich Gevorkyan; Osama M. Al- Habahbeh; Olga Shatalova; Ahmad Telfah; Evgeny Starkov; Nikolay A. Korenevskiy; Ashraf Shaqadan; Manafaddin Bashir Namazov; Ilyash Maksim; Marwan S. Mousa (Physical and Engineering Sciences in Medicine, 2025)

Functional Peptides in Targeted Cancer Therapy: Mechanisms, Delivery Strategies, and Clinical Perspectives - Wu Yan; Marwan Abdelmahmoud Abdelkarim Maki; Vasudevan Mani; Mogana R; Palanirajan Vijayaraj Kumar (International Journal of Peptide Research and Therapeutics, 2025)

Native Trees of the Mediterranean Region: Distribution, Diversity and Conservation Challenges - Bruno Fady; Anna-Maria Farsakoglou; Mercedes Caron; Khaled Abulaila; Jelena Aleksic; Sajad Alipour; Dalibor Balian; Heba Bedair; Faruk Bogunić; Marwan Cheikh Albassatneh; Rakefet David-Schwartz; Carmen Delgado Clavero; et al. (Current Forestry Reports, 2025)
Purpose of Review While 38% of tree species are at risk of extinction worldwide, their inventory and occurrence at ecologically and biogeographically meaningful scales is lacking in many parts of the world, including the biodiversity-rich Mediterranean region. Here, we provide presence/absence, extinction risk, biogeography and genetic diversity data of trees in 39 climatically and ecologically Mediterranean territories (so-called “botanical territories”) in North Africa, Western Asia and Southern Europe. Recent Findings The inventory includes 496 species and 147 subspecies from 50 families and 111 genera, including 48 species and 8 subspecies previously not considered as trees. We show that native tree species distribution is highly skewed across the tree of life with a few species-rich families such as the Rosaceae and the majority with less than 1% of all species. Endemism was not evenly distributed among botanical territories and neither was extinction risk, an assessment of which was lacking in almost half of the species. While no geographic trends were detectable, species richness was found to be positively correlated with botanical territory area and, when standardized by area, with habitat heterogeneity. Information on genetic diversity was lacking in two thirds of the species inventoried and mostly focused on species with economic importance. Summary Our data are open access and can be used by researchers and stakeholders for a wide range of purposes, including conservation and restoration. Our findings identified major native tree richness hotspots as well as key knowledge gaps and biases related to extinction risk and genetic diversity. Our findings also emphasize the importance of increased collaboration to support the conservation of Mediterranean forest trees.

Phosphocreatine Mitigates Doxorubicin-Induced Neurotoxicity in Rats by Regulating Mitochondrial Function and Apoptosis via the NF-κB/PGC-1α Pathway - Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Dalal Sanad Al-Mutairi; Zeyao Tang; Marwan Almoiliqy (NeuroMolecular Medicine, 2025)

How well do the reanalysis datasets capture hot and cold extremes and their trends in India? - Suman Bhattacharyya; Marwan A. Hassan; S. Sreekesh; Vandana Choudhary (Atmospheric Research, 2025)

Harnessing the Microbiome: CRISPR-Based Gene Editing and Antimicrobial Peptides in Combating Antibiotic Resistance and Cancer - Radwa A. Amen; Yaser M. Hassan; Rawan A. Essmat; Rana H. Ahmed; Marwan M. Azab; Nadia R. Shehata; Mariam M. Elgazzar; Wael M. El-Sayed (Probiotics and Antimicrobial Proteins, 2025)
The growing crisis of antibiotic resistance and the increasing incidence of cancer have prompted the exploration of innovative approaches, such as gene editing and antimicrobial peptides (AMPs). The human microbiome is integral to various aspects of health, disease, and therapeutic development, influencing metabolic pathways, immune function, and pathogen resistance. Recent advances in gene editing technologies, particularly CRISPR (clustered regularly interspaced short palindromic repeats), have opened new avenues for leveraging the microbiome to address complex medical challenges, including combating multidrug-resistant pathogens and cancer. The microbiome plays a crucial role in combating antibiotic resistance by modulating microbial communities, influencing pathogen survival and susceptibility to treatments. This review explores the microbiome’s dynamic role in metabolic regulation, its contribution to cancer management, and how AMPs help maintain homeostasis and exhibit emerging anticancer properties, supported by both preclinical findings and clinical evidence. Additionally, CRISPR-based microbiome engineering offers potential to enhance host-microbiome interactions, optimizing therapeutic outcomes. The integration of microbiome metagenomics and proteomics has led to the discovery of novel AMPs with targeted anticancer effects. Innovative strategies, such as engineered probiotics and CRISPR-based microbiome engineering, present exciting prospects for next-generation therapies. Despite these advances, the translation of microbiome-based therapies into clinical settings remains challenging due to ethical, regulatory, and ecological hurdles. This review underscores the transformative potential of microbiome-based interventions, emphasizing the role of personalized medicine in maximizing therapeutic efficacy. Furthermore, we also address critical research gaps, limitations, and future directions, including optimizing AMP stability, delivery, and bioavailability, as well as overcoming the regulatory and ethical challenges in clinical translation.

Evaluation of the shallow hydrothermal system in Jaboi Volcano based on the combination of remote sensing and geophysical measurements - Muhammad Yanis; Muhammad Isa; Nasrullah Zaini; Faisal Abdullah; Muksin Umar; Marwan; Cutti Zahrati; Bondan Galih Dewanto; Riski Ananda; Azman Abdul Ghani (Geosciences Journal, 2025)

Association of PLCE1 (rs7922612) and COL4A3 (rs375290088) Genetic Variants with the Risk of Nephrotic Syndrome in Egyptian Pediatric Patients - Wafaa A. Mokhtar; Afaf M. Elsaid; Ahmed M. Elrefaey; Marwan Mahmood Saleh; Magdy M. Youssef (Biochemical Genetics, 2025)

Phthalate ester contamination in groundwater at the Himalayan-Potohar Interface: health risks in Rawalpindi, Pakistan - Hidayat Ullah; Bakht Rawan; Marwan Ullah; Muhammad Ibrar Shinwari; Thiago Machado da Silva Acioly; Patricio De los Rios-Escalante; Fedlu Kedir Sabir; Muhammad Ilyas (Environmental Monitoring and Assessment, 2025)

Stereotyping the Chinese in Arab Nations:Effects of media use, perceived realism, and perceived Chinese-Arab relations - Muhammad Khalil Khan; Marwan H. Sallam; Cornelius B. Pratt; Tahir Farid (The Social Science Journal, 2025)

Functional connectivity of sensory and executive function networks during a story listening task is related to parent/child interaction during joint reading: a functional MRI diffusion map study - Tzipi Horowitz Kraus; Marwan Bebar; Adi Jacobson; John Hutton (Brain Imaging and Behavior, 2025)
The quality of parent–child interaction during shared reading (“shared reading quality”) is strongly linked to cognitive and relational benefits. However, the relationship between shared reading quality and activation and synchronization of reading-related brain networks has not yet been characterized. The current study involved 22 4-year-old girls who completed functional MRI including a validated stories listening task, and a primary parent. Prior to MRI, video observation of the parent and child reading together was conducted and later coded using a standardized scoring form quantifying parent–child verbal and nonverbal interaction. Behavioral measures included demographics and a maternal depression scale. To achieve this goal, fMRI stories-listening data was utilized to create a diffusion maps algorithm and then to classify the level of parent–child interaction during the shared reading observation. The algorithm clustered children with higher parent–child engagement scores with fMRI diffusion patterns in regions of the brain known to support reading. This study establishes proof-of-concept that applying this diffusion maps algorithm to brain functional connectivity data can reliably predict parent–child interaction during shared book reading. It also suggests that an algorithmic approach may be a novel, data-driven means to quantify parent–child interaction in different contexts (e.g., reading, play) and populations.

Capturing social sensing of farming activities for policymaking in fragile contexts - Nadir Ahmed Elagib; Bashir M. Ahmed; Hussein M. Sulieman; Abbas E. Rahma; Marwan M.A. Ali; Karl Schneider (Journal of Rural Studies, 2025)

Gold nanocomposites in colorectal cancer therapy: characterization, selective cytotoxicity, and migration inhibition - Kin Fai Tan; Le Yi Chia; Marwan Abdelmahmoud Abdelkarim Maki; Shiau-Chuen Cheah; Lionel Lian Aun In; Palanirajan Vijayaraj Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparative study of lignin from patchouli waste fibers and spent coffee grounds as biofillers in poly(3-hydroxybutyrate-co-3-hydroxyvalerate)-based biodegradable packaging materials - Syaifullah Muhammad; Rahul Dev Bairwan; H.P.S. Abdul Khalil; Marwan Marwan; Mardiana Idayu Ahmad; C.K. Abdullah (Bioresource Technology Reports, 2025)

Beyond the Injury: How Does Smoking Impair Stem Cell-Mediated Repair Mechanisms? A Dual Review of Smoking-Induced Stem Cell Damage and Stem Cell-Based Therapeutic Applications - Mario Karam; Sarah Aqel; Mohammad Z. Haider; Aseela Fathima; Adib Charafedine; Mira Abou Daher; Abdullah Shaito; Marwan El-Sabban; Jessica Saliba (Stem Cell Reviews and Reports, 2025)

Correction to: Appraising flood risk and inundation extent using GIS-aided 2D hydraulic modeling in Nepal Himalaya: a case of West Rapti river Basin - Amrit Prasad Sharma; Xudong Fu; Giri R. Kattel; Tirtha Raj Adhikari; Marwan A. Hassan (Modeling Earth Systems and Environment, 2025)

Appraising flood risk and inundation extent using GIS-aided 2D hydraulic modeling in Nepal Himalaya: a case of West Rapti River Basin - Amrit Prasad Sharma; Xudong Fu; Giri R. Kattel; Tirtha Raj Adhikari; Marwan A. Hassan (Modeling Earth Systems and Environment, 2025)

Liquefaction Behavior of Suction Bucket Foundations for Wind Turbines Under Soil Variability - Mohammed Jasim Khammas Issa; Marwan Abdelsalam; Liqaa Hashim Khudhair; Mohsen Seyedi; Mohammad Shouib Anwar Khan (Geotechnical and Geological Engineering, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Phosphocreatine-mediated enhancement of mitochondrial function for accelerated healing of diabetic foot ulcers through the PGC-1α-NRF-1 signaling pathway - Eskandar Qaed; Marwan Almoiliqy; Wu Liu; Jingyu Wang; Haitham Saad Al-mashriqi; Waleed Aldahmash; Mueataz A. Mahyoub; Zeyao Tang (Tissue and Cell, 2025)

A discrete fracture model for coupled simulation of water flow and electrical current in fractured vadose zone - Behshad Koohbor; Pierre Fischer; Marwan Fahs; Abderrahim Jardani; Anis Younes; Hervé Jourde (Journal of Hydrology, 2025)

Unleashing the potential of Genistein and its derivatives as effective therapeutic agents for breast cancer treatment - Eskandar Qaed; Wu Liu; Marwan Almoiliqy; Rawan Mohamed; Zeyao Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Characterising Local Flood‐Inducing Heavy Rainfall Through Daily Weather Types and Large‐Scale Climatic Patterns: Aotearoa New Zealand Study Case - Andrea Pozo; Matthew Wilson; Marwan Katurji; Laura Cagigal; Fernando J. Méndez; Emily Lane (International Journal of Climatology, 2025)
Flooding is the most frequent natural hazard in Aotearoa New Zealand and the second most costly after earthquakes. It will change in frequency and intensity, becoming more extreme as climate change impacts are realised. The main inundation driver is heavy rainfall. In this study, flood‐inducing heavy rainfall is characterised locally by applying synoptic climatological techniques, using the study case of Aotearoa New Zealand. Extending on previous work in the field, a new set of 49 daily weather types (DWTs) is proposed for New Zealand, based on mean sea level pressure (MLSP) and 500 hPa geopotential height (500GH) (predictor variables). The role of the DWTs, the large‐scale climatic patterns (LSCPs) known to influence rainfall variability, and the wind conditions (as an additional explanatory variable since they play an essential role in the development of these events) as heavy rainfall and flooding (predictand variables) drivers is investigated using the Wairewa catchment (Little River, Canterbury) as the study site. Heavy rainfall is represented through its temporal and spatial features, based on two rainfall datasets (a rain gauge and a gridded product obtained by the Weather Research and Forecasting (WRF) numerical model). Useful relationships are found between the predictor and the predictand variables. Also, the predictor variables' temporal variability (interannual and intra‐annual variability, seasonality) plays a key role, translating to the temporal variability of heavy rainfall and flooding. The proposed synoptic climatological approach provides qualitative and quantitative value, displaying the range of weather and climatic configurations leading to different types of storms and flooding and helping in their identification and understanding.

Efficient uranium capture from water with date palm seed biomass: green remediation - Mohammed A. Al-Anber; Hadeel Almazaydeh; Idrees F. Al-Momani; Suresh Sagadevan; Marwan S. Mousa; Dinara Sobola; Abhinav Kumar (Environmental Science and Pollution Research, 2025)

Back-analysis of the 2000 Yigong dam breach flood morphodynamics: Challenges and promises - Yunlong Lei; Marwan A. Hassan; Giorgio Rosatti; Luigi Fraccarollo; Daniel Zugliani; Xudong Fu; Chunhong Hu (Geomorphology, 2025)

Monitoring sewage and effluent water is an effective approach for the detection of the mobile colistin resistance genes (mcr) and associated bacterial hosts in the human population and environment in the USA - Jouman Hassan; Marwan Osman; Tongzhou Xu; Thierry Naas; Steven J. Schiff; David Mann; Malak A. Esseili; Xiangyu Deng; Issmat I. Kassem (Environmental Pollution, 2025)

Prediction of permeability coefficient of soil using hybrid artificial neural network models - Majid M. Kharnoob; Tarak Vora; A. K. Dasarathy; Ish Kapila; Marwan Kheimi; Srinivasa Rao Rapeti (Modeling Earth Systems and Environment, 2025)

Positive Selection Shapes Breast Cancer Tumor Suppressor Genes: Unveiling Insights into BRCA1, BRCA2, and MDC1 Stability - Youssef M. Fadel; Marwan Khaled; Mohamed Emam; Nour H. Marzouk; Sief El-Din Sobih; Habiba Abd-Elaty; Wafaa M. Elrashedy; Gehad Mostafa; Salma alm eldeen; Mohaned Bador; Agostinho Antunes; Mohamed El hadidi (Journal of Molecular Evolution, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Comparative analysis of the silver-gold and copper-titanium dioxide hybrid nanoparticles impact on flow and heat transfer of the pulsatile blood in occluded cerebral artery - Nahid Najafi; Wala Almosawy; Marwan S. Abbas; Arash Goligerdian; Mohammad Najafi; Negar Abdi; Aram Ardalan; Saman Aminian (Journal of Thermal Biology, 2025)

Toward flow forces acting on a step-pool unit - Chendi Zhang; Marwan A. Hassan; Yuncheng Xu (Geomorphology, 2025)

On the flow behaviour of unconfined dual porosity aquifers with sloping base - Konstantinos N. Moutsopoulos; John N.E. Papaspyros; Antonis D. Koussis; Frederick Delay; Marwan Fahs (Advances in Water Resources, 2025)

Intensifying droughts render more Sahel drylands unsuitable for cultivation - Nadir Ahmed Elagib; Marwan M.A. Ali; Ammar Ahmed Musa (Science of The Total Environment, 2024)

Tetrachloroethylene exposure and neurobehavioral performance among children living near multiple contamination sites - Marwan Alajlouni; Ian Kurz; Jung Hyun Lee; Alaina K. Bryant; Jackson Pechin; Brandon Tso; Abigail Valdez; Sujana Vemuru; Monica Bozymski; Bethaney Latham; Stephanie Littell; Samantha Mills; et al. (Science of The Total Environment, 2024)

Isothermal thermoluminescence dating of speleothem growth – A case study from Bleßberg cave 2, Germany - Junjie Zhang; Jennifer Klose; Denis Scholz; Norbert Marwan; Sebastian F.M. Breitenbach; Lutz Katzschmann; Dennis Kraemer; Sumiko Tsukamoto (Quaternary Geochronology, 2024)

MBOAT7 expression is associated with disease progression in COVID-19 patients - Eman Radwan; Ahmed Abdelaziz; Manal A. M. Mandour; Abdel-Raheim M. A. Meki; Maha M. El-kholy; Marwan N. Mohamed (Molecular Biology Reports, 2024)
Background and aim The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in late 2019 caused a pandemic of acute respiratory disease, named coronavirus disease 2019 (COVID-19). COVID-19 became one of the most challenging health emergencies, hence the necessity to find different prognostic factors for disease progression, and severity. Membrane bound O-acyltransferase domain containing 7 (MBOAT7) demonstrates anti-inflammatory effects through acting as a fine-tune regulator of the amount of cellular free arachidonic acid. We aimed in this study to evaluate MBOAT7 expression in COVID-19 patients and to correlate it with disease severity and outcomes. Methods This case-control study included 56 patients with confirmed SARS-CoV-2 diagnosis and 28 control subjects. Patients were further classified into moderate (n = 28) and severe (n = 28) cases. MBOAT7, tumor necrosis factor-α (TNF-α), and interleukin-1ß (IL-1ß) mRNA levels were evaluated in peripheral blood mononuclear cells (PBMC) samples isolated from patients and control subjects by real time quantitative polymerase chain reaction (RT-qPCR). In addition, circulating MBOAT7 protein levels were assayed by enzyme-linked immunosorbent assay (ELISA). Results Significant lower levels of circulating MBOAT7 mRNA and protein were observed in COVID-19 patients compared to control subjects with severe COVID-19 cases showing significant lower levels compared to moderate cases. Moreover, severe cases showed a significant upregulation of TNF-α and IL-1ß mRNA. MBOAT7 mRNA and protein levels were significantly correlated with inflammatory markers (TNF-α, IL-1ß, C-reactive protein (CRP), and ferritin), liver enzymes, severity, and oxygen saturation levels. Conclusion COVID-19 is associated with downregulation of MBAOT7, which correlates with disease severity.

Modeling fluid flow in heterogeneous porous media with physics-informed neural networks: Weighting strategies for the mixed pressure head-velocity formulation - Ali Alhubail; Marwan Fahs; François Lehmann; Hussein Hoteit (Advances in Water Resources, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Polycyclic aromatic hydrocarbons in indoor mosques dust in Saudi Arabia: Levels, source apportionment, human health and carcinogenic risk assessment for congregators - Mansour A. Alghamdi; Salwa K. Hassan; Waleed H. Shetaya; Marwan Y. Al Sharif; Javed Nawab; Mamdouh I. Khoder (Science of The Total Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Assimilating multivariate remote sensing data into a fully coupled subsurface-land surface hydrological model - Samira Sadat Soltani; Behzad Ataie-Ashtiani; Ahmad Al Bitar; Craig.T. Simmons; Anis Younes; Marwan Fahs (Journal of Hydrology, 2024)

Phosphocreatine attenuates doxorubicin-induced nephrotoxicity through inhibition of apoptosis, and restore mitochondrial function via activation of Nrf2 and PGC-1α pathways - Eskandar Qaed; Ahmed Almaamari; Marwan almoiliqy; Eman Alyafeai; Marwa Sultan; Waleed Aldahmash; Mueataz A. Mahyoub; Zeyao Tang (Chemico-Biological Interactions, 2024)

Subject-specific trunk segmental masses prediction for musculoskeletal models using artificial neural networks - Tao Liu; Marwan El-Rich (Medical & Biological Engineering & Computing, 2024)

Quadruplex qPCR for detection and discrimination of C. Coli,C. fetus, and C. Jejuni from other Campylobacter species in chicken and sheep meat - Marwan Abu-Halaweh; Eman Al-bsoul (Brazilian Journal of Microbiology, 2024)

A conceptual model on the influence of logjam formation on longitudinal and lateral sediment dynamics in forested streams - Marwan A. Hassan; Conor McDowell; Stephen Bird; David A. Reid; Mike Turley; Dan Hogan (Geomorphology, 2024)

Development of eco-friendly coating for the fabrication of high performing loose nanofiltration membranes for dye-contaminated wastewater treatment - Abedalkader Alkhouzaam; Marwan Khraisheh (Desalination, 2024)

Screening of pslA and pelB Biofilm-Producing Genes from Pseudomonas Isolated from Clinical Samples - Zahra Soleymani-Fard; Mehdi Hassanshahian; Saade Abdalkareem Jasim; Walid Kamal Abdelbasset; Rustem Adamovich Shichiyakh; Baydaa Abed Hussein; Hamzah H. Kzar; Dhameer A. Mutlak; Aiman Mohammed Baqir Al-Dhalimy; Marwan Mahmood Saleh; Moaed E. Al-Gazally; Yasser Fakri Mustafa (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Anti-IL-17 bioactivity-guided fractionation of a pine bio-oil: Chemical characterization and impact on HaCaT human keratinocytes gene expression - Marwan Gagaa; Heather Koehler; Manuel Garcia-Perez; Martha-Estrella García-Pérez (Bioresource Technology Reports, 2024)

Salmonella serovars trend in poultry Malaysia from 2011 to 2020 - Muhammad Marwan Ibrahim; Mohammad Bohari Jusoh; Farid Zamani Che Rose; Mohammad Masrin Azami; Roseliza Roslee (Veterinary Research Communications, 2024)

Enhancing agency and empowerment in agricultural development projects: A synthesis of mixed methods impact evaluations from the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) - Agnes R. Quisumbing; Ruth Meinzen-Dick; Hazel J. Malapit; Greg Seymour; Jessica Heckert; Cheryl Doss; Nancy Johnson; Deborah Rubin; Giang Thai; Gayathri Ramani; Emily Myers; Agnes Quisumbing; et al. (Journal of Rural Studies, 2024)

Development and validation of a novel ankle joint musculoskeletal model - Tao Liu; Andrea Dimitrov; Nadr Jomha; Samer Adeeb; Marwan El-Rich; Lindsey Westover (Medical & Biological Engineering & Computing, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Exceptional anticancer photodynamic properties of [1,4-Bis(3,6,9,12-Tetraoxatridec-1-yloxy)phthalocyaninato]zinc(II) - Christophe Nguyen; Isabelle Toubia; Kamel Hadj-Kaddour; Lamiaa M.A. Ali; Laure Lichon; Charlotte Cure; Stéphane Diring; Marwan Kobeissi; Fabrice Odobel; Magali Gary-Bobo (Journal of Photochemistry and Photobiology B: Biology, 2024)

Evaluation and bias correction of CRU TS4.05 potential evapotranspiration across vast environments with limited data - Nadir Ahmed Elagib; Marwan M.A. Ali; Karl Schneider (Atmospheric Research, 2024)

An efficient fully Crouzeix-Raviart finite element model for coupled hydro-mechanical processes in variably saturated porous media - Lingai Guo; Anis Younes; Marwan Fahs; Hussein Hoteit (Advances in Water Resources, 2024)

Modeling rainfall-induced landslide using the concept of local factor of safety: Uncertainty propagation and sensitivity analysis - Rashad Abbasov; Marwan Fahs; Anis Younes; Hossein Nowamooz; Knut Jørgen Måløy; Renaud Toussaint (Computers and Geotechnics, 2024)

Response of a small, forested stream to a large input of sediment - Conor McDowell; Marwan A. Hassan (Geomorphology, 2024)

Towards sustainable management of end-of-life membranes: Novel transformation of end of life (EoL) reverse osmosis membranes for efficient dye/salt separation - Abedalkader Alkhouzaam; Marwan Khraisheh (Desalination, 2024)

Enhancement micro filler spent coffee grounds in catalyst - chemically modified bast fibers reinforced biodegradable materials - M. Marwan; Eti Indarti; Rahul Dev Bairwan; H.P.S. Abdul Khalil; C.K. Abdullah; Azfaralariff Ahmad (Bioresource Technology Reports, 2024)

Data-driven approaches for estimation of sediment discharge in rivers - Marwan Kheimi (Earth Science Informatics, 2024)

Uncovering the Therapeutic Potential of Phosphocreatine in Diabetic Retinopathy: Mitigating Mitochondrial Dysfunction and Apoptosis via JAK2/STAT3 Signaling Pathway - Eskandar Qaed; Eman Alyafeai; Ahmed Al-Maamari; Mohamed Y. Zaky; Marwan Almoiliqy; Bandar Al-Hamyari; Abdullah Qaid; Saeed Yafei; Waleed Aldahmash; Mueataz A. Mahyoub; Fuhan Wang; Le Kang; et al. (Journal of Molecular Neuroscience, 2024)

Estimating population density using open-access satellite images and geographic information system: Case of Al Ain city, UAE - M.M. Yagoub; Yacob T. Tesfaldet; Tareefa AlSumaiti; Naeema Al Hosani; Marwan G. Elmubarak (Remote Sensing Applications: Society and Environment, 2024)

Effects of n-decane substitution on structure and extinction limits of formic acid diffusion flames - Adamu Alfazazi; Jiajun Li; Chaochen Xu; Et-touhami Es-sebbar; Xiaoyuan Zhang; Marwan Abdullah; Mourad Younes; S. Mani Sarathy; Bassam Dally (Fuel, 2024)

Not all parents are the same: Diverse strategies of symbiont transmission in seaweeds - Syukur Syukur; Joanna Richmond; Marwan E. Majzoub; Jadranka Nappi; Suhelen Egan; Torsten Thomas (Environmental Microbiology, 2024)
Different marine seaweed species have been shown to harbour specific bacterial communities, however, the extent to which vertical symbiont transmission from parents to offspring contributes to host‐specificity is unclear. Here we use fluorescence and electron microscopy as well as 16S rRNA gene‐based community analysis to investigate symbiont transmission in members of the three major seaweed groups (green Chlorophyta , red Rhodophyta and brown Phaeophyceae ). We found seaweeds employ diverse strategies to transfer symbionts to their progeny. For instance, the green Ulva australis does not appear to have the capacity for vertical transmission. In contrast, the brown Phyllospora comosa adopts a non‐selective vertical transmission. The red Delisea pulchra demonstrates weak selectivity in symbiont transmission, while the brown Hormosira banksii exhibits a strongly selective symbiont transfer. Mucilage on the gametes appears to facilitate vertical transmission and transferred bacteria have predicted properties that could support early development of the seaweeds. Previous meta‐analysis has indicated that vertical transmission is rare in aquatic compared to terrestrial environments, however, our results contribute to the growing evidence that this might not be the case and that instead vertical transmission with various degrees of symbiont selection occurs in the ecologically important group of seaweeds.

The impact of interspecific competition on the genomic evolution of Phaeobacter inhibens and Pseudoalteromonas tunicata during biofilm growth - Weizhi Song; Shan Zhang; Marwan E. Majzoub; Suhelen Egan; Staffan Kjelleberg; Torsten Thomas (Environmental Microbiology, 2024)
Interspecific interactions in biofilms have been shown to cause the emergence of community‐level properties. To understand the impact of interspecific competition on evolution, we deep‐sequenced the dispersal population of mono‐ and co‐culture biofilms of two antagonistic marine bacteria ( Phaeobacter inhibens 2.10 and Pseudoalteromononas tunicata D2). Enhanced phenotypic and genomic diversification was observed in the P. tunicata D2 populations under both mono‐ and co‐culture biofilms in comparison to P. inhibens 2.10. The genetic variation was exclusively due to single nucleotide variants and small deletions, and showed high variability between replicates, indicating their random emergence. Interspecific competition exerted an apparent strong positive selection on a subset of P. inhibens 2.10 genes (e.g., luxR , cobC , argH , and sinR ) that could facilitate competition, while the P. tunicata D2 population was genetically constrained under competition conditions. In the absence of interspecific competition, the P. tunicata D2 replicate populations displayed high levels of mutations affecting the same genes involved in cell motility and biofilm formation. Our results show that interspecific biofilm competition has a complex impact on genomic diversification, which likely depends on the nature of the competing strains and their ability to generate genetic variants due to their genomic constraints.

Clinical and nutritional management of very-low-calorie ketogenic diet (VLCKD) in patients with psoriasis and obesity: a practical guide for the nutritionist - Luigi Barrea; Massimiliano Caprio; Elisabetta Camajani; Ludovica Verde; Ausilia Elce; Evelyn Frias-Toral; Florencia Ceriani; Gabriela Cucalón; Eloisa Garcia-Velasquez; Marwan El Ghoch; Annamaria Colao; Silvia Savastano; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Speleothem growth and stable carbon isotopes as proxies of the presence and thermodynamical state of glaciers compared to modelled glacier evolution in the Alps - Vanessa Skiba; Guillaume Jouvet; Norbert Marwan; Christoph Spötl; Jens Fohlmeister (Quaternary Science Reviews, 2023)

Nano cerium oxide and cerium/zinc nanocomposites characterization and therapeutic role in combating obesity via controlling oxidative stress and insulin resistance in rat model - Ahmed M.A. El-Seidy; Marwan A. Elbaset; Fatma A.A. Ibrahim; Sherif A. Abdelmottaleb Moussa; Samir AE Bashandy (Journal of Trace Elements in Medicine and Biology, 2023)

Impact of COVID-19 vaccination on saliva immune barriers: IgA, lysozyme, and lactoferrin - Hanadi H. Abdul-Kareem; Marwan Y. Al-Maqtoofi; Ahmed A. Burghal (Archives of Virology, 2023)

Differential priority effects impact taxonomy and functionality of host‐associated microbiomes - Jadranka Nappi; Priscila Goncalves; Tahsin Khan; Marwan E. Majzoub; Anna Sophia Grobler; Ezequiel M. Marzinelli; Torsten Thomas; Suhelen Egan (Molecular Ecology, 2023)
Most multicellular eukaryotes host complex communities of microorganisms, but the factors that govern their assembly are poorly understood. The settlement of specific microorganisms may have a lasting impact on community composition, a phenomenon known as the priority effect. Priority effects of individual bacterial strains on a host's microbiome are, however, rarely studied and their impact on microbiome functionality remains unknown. We experimentally tested the effect of two bacterial strains ( Pseudoalteromonas tunicata D2 and Pseudovibrio sp. D323) on the assembly and succession of the microbial communities associated with the green macroalga Ulva australis . Using 16S rRNA gene sequencing and qPCR, we found that both strains exert a priority effect, with strain D2 causing initially strong but temporary taxonomic changes and strain D323 causing weaker but consistent changes. Consistent changes were predominately facilitatory and included taxa that may benefit the algal host. Metagenome analyses revealed that the strains elicited both shared (e.g., depletion of type III secretion system genes) and unique (e.g., enrichment of antibiotic resistance genes) effects on the predicted microbiome functionality. These findings indicate strong idiosyncratic effects of colonizing bacteria on the structure and function of host‐associated microbial communities. Understanding the idiosyncrasies in priority effects is key for the development of novel probiotics to improve host condition.

Performance investigation of a tubular distiller using parabolic concentrator with various modifications - Swellam W. Sharshir; Zhanhui Yuan; Marwan Elsharkawy; Mohamed A. Hamada; Ahmed Swidan; Gamal B. Abdelaziz; A.S. Abdullah; M.O.A. El-Samadony (Process Safety and Environmental Protection, 2023)

A mixed pressure-velocity formulation to model flow in heterogeneous porous media with physics-informed neural networks - François Lehmann; Marwan Fahs; Ali Alhubail; Hussein Hoteit (Advances in Water Resources, 2023)

Simulation of temperature swing adsorption process to purify hydrogen for fuel cell uses by SAPO34 as adsorbent - Marwan Kheimi; Sultan K. Salamah (Chemosphere, 2023)

Validation of strain/energy-based pore pressure model in one-dimensional response analyses using centrifuge tests - Marwan Khashila; Mourad Karray; Mahmoud N. Hussien; Jenny Ramirez; Mohamed Chekired (Soil Dynamics and Earthquake Engineering, 2023)

Coupled fluid flow, solute transport and dissolution processes in discrete fracture networks: An advanced Discontinuous Galerkin model - Sara Tabrizinejadas; Anis Younes; Hussein Hoteit; Jerome Carrayrou; Marwan Fahs (Advances in Water Resources, 2023)

Thermal design and zeotropic working fluids mixture selection optimization for a solar waste heat driven combined cooling and power system - Marwan Kheimi; Sultan K. Salamah; Hisham A. Maddah; Mohd Mustafa Al Bakri Abdullah (Chemosphere, 2023)

Effect of temperature on convective-reactive transport of CO2 in geological formations - Sara Tabrizinejadas; Marwan Fahs; Hussein Hoteit; Anis Younes; Behzad Ataie-Ashtiani; Craig T. Simmons; Jerome Carrayrou (International Journal of Greenhouse Gas Control, 2023)

Coupling mixed hybrid and extended finite element methods for the simulation of hydro-mechanical processes in fractured porous media - Lingai Guo; Marwan Fahs; Behshad Koohbor; Hussein Hoteit; Anis Younes; Rui Gao; Qian Shao (Computers and Geotechnics, 2023)

Evaluation of supply air temperature control performance with different control strategies at air handling units - Zufen Wang; Marwan R. Hashem; Li Song; Gang Wang (Building and Environment, 2023)

Hydro-Geoheritage and Paleo-Cultural Footprints Associated with the Socio-Economic Coherence for a Potential Jericho Geopark - Marwan Ghanem; África de la Hera-Portillo; Alsharifa Hind Mohammad; Noreddine Laftouhi (Geoheritage, 2023)

Vertical electrical sounding for revealing the groundwater resources in the geothermal spring of Jaboi volcano - Muhammad Yanis; Nasrullah Zaini; Faisal Abdullah; Muhammad Isa; Marwan Marwan; Syafrizal Idris; Andri Yadi Paembonan; Riski Ananda; Muzakir Zainal; Azman Abdul Ghani; Deni Saputra (Acta Geophysica, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Transglutaminase cross-linking on dairy proteins: Functionalities, patents, and commercial uses - Angella Velazquez-Dominguez; Manon Hiolle; Marwan Abdallah; Guillaume Delaplace; Paulo P.S. Peixoto (International Dairy Journal, 2023)

Meta-analysis of a large bedload transport rate dataset - Sebastian Schwindt; Beatriz Negreiros; Bridget Ochuko Mudiaga-Ojemu; Marwan A. Hassan (Geomorphology, 2023)

The influence of coarse particle abundance and spatial distribution on sediment transport and cluster evolution in steep channels under sediment-starved conditions - Wenqi Li; Matteo Saletti; Marwan A. Hassan; Joel P.L. Johnson; Julia Carr; Cormac Chui; Kejun Yang (CATENA, 2023)

Knowledge of Human Papillomavirus (HPV), Attitudes, and Practices Towards Anti-HPV Vaccination Among Israeli Nurses - Rola Khamisy-Farah; Maher Endrawis; Marwan Odeh; Ruba Tuma; Matteo Riccò; Francesco Chirico; Nicola Luigi Bragazzi (Journal of Cancer Education, 2023)

Stochastic (S[ARIMA]), shallow (NARnet, NAR-GMDH, OS-ELM), and deep learning (LSTM, Stacked-LSTM, CNN-GRU) models, application to river flow forecasting - Marwan Kheimi; Mohammad Almadani; Mohammad Zounemat-Kermani (Acta Geophysica, 2023)

Natural resource curse: A literature survey and comparative assessment of regional groupings of oil-rich countries - Marwan Alssadek; James Benhin (Resources Policy, 2023)

Nutritional management of type 2 diabetes in subjects with obesity: an international guideline for clinical practice - Luigi Barrea; Claudia Vetrani; Massimiliano Caprio; Marwan El Ghoch; Evelyn Frias-Toral; Rucha J. Mehta; Verna Mendez; Eleonora Moriconi; Stavroula A. Paschou; Agnieszka Pazderska; Silvia Savastano; Annamaria Colao; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Prediction of shear strength for CFRP reinforced concrete beams without stirrups - Bahaa Elghandour; Reham Eltahawy; Marwan Shedid; Amr Abdelrahman (Engineering Structures, 2023)

The Role of Ferroptosis in the Pathogenesis of Osteoarthritis - Hussein Riyadh Abdul Kareem Al-Hetty; Sada Jasim Abdulameer; Maha Waleed Alghazali; Fatime Satar Sheri; Marwan Mahmood Saleh; Abduladheem Turki Jalil (The Journal of Membrane Biology, 2023)

Confusion assessment method accurately screens for hepatic encephalopathy and predicts short-term mortality in hospitalized patients with cirrhosis - Archita P. Desai; Devika Gandhi; Chenjia Xu; Marwan Ghabril; Lauren Nephew; Kavish R. Patidar; Noll L. Campbell; Naga Chalasani; Malaz Boustani; Eric S. Orman (Metabolic Brain Disease, 2023)

Influence of geology and topography on the occurrence of mine massive collapse—back-analysis of a historical collapse of chalk mine (France) - Marwan Al Heib; Nathalie Conil; Philippe Gombert (Bulletin of Engineering Geology and the Environment, 2023)

Verbesserter Stabilitätsansatz bei Dämmen unter Einbeziehung der teilgesättigten Zone - Dirk Fleischer; Ulf Helbig; Thomas Fichtner; Rene Blankenburg; Marwan El Masri; Peter-Wolfgang Gräber (WASSERWIRTSCHAFT, 2023)

Increased sample size provides novel insights into population structure of Mediterranean loggerhead sea turtles - Arzu Kaska; Gizem Koç; Doğan Sözbilen; Diryaq Salih; Ashraf Glidan; Abd Alati Elsowayeb; Almokhtar Saied; Dimitris Margaritoulis; Panagiota Theodorou; ALan Rees; Robin Snape; Annette Broderick; et al. (Conservation Genetics Resources, 2023)

Influence of enzymatic cross-linking on the apparent viscosity and molecular characteristics of casein micelles at neutral and acidic pH - Angella Velazquez-Dominguez; Marie Hennetier; Marwan Abdallah; Manon Hiolle; Fréderic Violleau; Guillaume Delaplace; Paulo Peres De Sa Peixoto (Food Hydrocolloids, 2023)

Regenerative Medicine for Polycystic Ovary Syndrome: Stem Cell-Based Therapies and Brown Adipose Tissue Activation - Mario Karam; Hélène Najjar; Marwan El Sabban; Aline Hamade; Fadia Najjar (Stem Cell Reviews and Reports, 2023)

Friction to Unconfined Compression Strength Correlation for Evaluating Capacity of Weak Rock Foundation Sockets - Sujatha Manoj; Deepankar Choudhury; Harry Poulos; Marwan Alzaylaie (Geotechnical and Geological Engineering, 2023)

Coffee consumption, health benefits and side effects: a narrative review and update for dietitians and nutritionists - Luigi Barrea; Gabriella Pugliese; Evelyn Frias-Toral; Marwan El Ghoch; Bianca Castellucci; Sebastián Pablo Chapela; María de los Angeles Carignano; Daniela Laudisio; Silvia Savastano; Annamaria Colao; Giovanna Muscogiuri (Critical Reviews in Food Science and Nutrition, 2023)

Plant-mediated synthesis of sphalerite (ZnS) quantum dots, Th1-Th2 genes expression and their biomedical applications - Walid Theib Mohammad; Hajar Alijani; Pawan Faris; Ehsan Salarkia; Mahin Naderifar; Majid Reza Akbarizadeh; Nooshin Hashemi; Siavash Iravani; Abduladheem Turki Jalil; Marwan Mahmood Saleh; Amirhossein Fathi; Mehrdad Khatami (South African Journal of Botany, 2023)

High seroprevalence of SARS-CoV-2 antibodies in household cats and dogs of Lebanon - Sara Khalife; Marwan Abdallah (Research in Veterinary Science, 2023)

Thermal energy storage using phase change materials in building applications: A review of the recent development - Swellam W. Sharshir; Abanob Joseph; Marwan Elsharkawy; Mohamed A. Hamada; A.W. Kandeal; Mohamed R. Elkadeem; Amrit Kumar Thakur; Yanbao Ma; Moustapha Eid Moustapha; Maher Rashad; Müslüm Arıcı (Energy and Buildings, 2023)

Spatial coherence patterns of extreme winter precipitation in the U.S. - Abhirup Banerjee; Matthias Kemter; Bedartha Goswami; Bruno Merz; Jürgen Kurths; Norbert Marwan (Theoretical and Applied Climatology, 2023)
Extreme precipitation events have a significant impact on life and property. The U.S. experiences huge economic losses due to severe floods caused by extreme precipitation. With the complex terrain of the region, it becomes increasingly important to understand the spatial variability of extreme precipitation to conduct a proper risk assessment of natural hazards such as floods. In this work, we use a complex network-based approach to identify distinct regions exhibiting spatially coherent precipitation patterns due to various underlying climate mechanisms. To quantify interactions between event series of different locations, we use a nonlinear similarity measure, called the edit-distance method, which considers not only the occurrence of the extreme events but also their intensity, while measuring similarity between two event series. Using network measures, namely, degree and betweenness centrality, we are able to identify the specific regions affected by the landfall of atmospheric rivers in addition to those where the extreme precipitation due to storm track activity is modulated by different mountain ranges such as the Rockies and the Appalachians. Our approach provides a comprehensive picture of the spatial patterns of extreme winter precipitation in the U.S. due to various climate processes despite its vast, complex topography.

Microplastic and oil pollutant agglomerates synergistically intensify toxicity in the marine fish, Asian seabass, Lates calcalifer - Erma Suryani Sahabuddin; Ayesha Noreen; Hamid Mahmood Abdullah Daabo; Mahmoud Kandeel; Marwan Mahmood Saleh; Zahraa Haleem Al-qaim; Mohammed Abed Jawad; Ramaswamy Sivaraman; Mohammed N. Fenjan; Yasser Fakri Mustafa; Aadel Heidary; Safoura Abarghouei; et al. (Environmental Toxicology and Pharmacology, 2023)

Three decades of wildlife-vehicle collisions in a protected area: Main roads and long-distance commuting trips to migratory prey increase spotted hyena roadkills in the Serengeti - Marwan Naciri; Aimara Planillo; Morgane Gicquel; Marion L. East; Heribert Hofer; Sonja Metzger; Sarah Benhaiem (Biological Conservation, 2023)

Soil-bacteria-mediated eco-friendly synthesis of ceramic nanostructure - Eman Alhomaidi; Pawan Faris; H. Saja; Abduladheem Turki Jalil; Marwan Mahmood Saleh; M. Khatami (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Early detection of adverse conditions in deep excavations using statistical process control - Dina Al Suwaidi; Salah Haridy; Marwan Al Zaylaie; Mohammad Shamsuzzaman; Hamdi Bashir; Ahmed Maged; Mohamed G. Arab (Innovative Infrastructure Solutions, 2023)

Combining harmonic pumping with a tracer test for fractured aquifer characterization - Arezou Dodangeh; Mohammad Mahdi Rajabi; Marwan Fahs (Hydrogeology Journal, 2023)

Polycyclic aromatic hydrocarbons in the surface water and sediment along Euphrates River system: Occurrence, sources, ecological and health risk assessment - Ruqayah Ali Grmasha; Marwan H. Abdulameer; Csilla Stenger-Kovács; Osamah J. Al-sareji; Zaid Al-Gazali; Raed A. Al-Juboori; Mónika Meiczinger; Khalid S. Hashim (Marine Pollution Bulletin, 2023)

Interconnection between the Indian and the East Asian summer monsoon: Spatial synchronization patterns of extreme rainfall events - Shraddha Gupta; Zhen Su; Niklas Boers; Jürgen Kurths; Norbert Marwan; Florian Pappenberger (International Journal of Climatology, 2023)
A deeper understanding of the intricate relationship between the two components of the Asian summer monsoon (ASM)—the Indian summer monsoon (ISM) and the East Asian summer monsoon (EASM)—is crucial to improve the subseasonal forecasting of extreme precipitation events. Using an innovative complex network‐based approach, we identify two dominant synchronization pathways between ISM and EASM—a southern mode between the Arabian Sea and southeastern China occurring in June, and a northern mode between the core ISM zone and northern China which peaks in July—and their associated large‐scale atmospheric circulation patterns. Furthermore, we discover that certain phases of the Madden–Julian oscillation and the lower frequency mode of the boreal summer intraseasonal oscillation (BSISO) seem to favour the overall synchronization of extreme rainfall events between ISM and EASM while the higher‐frequency mode of the BSISO is likely to support the shifting between the modes of ISM–EASM connection.

Aggregation behaviour of black carbon in aquatic solution: Effect of ionic strength and coexisting metals - Kiran Dhangar; Manish Kumar; Marwan Aouad; Jurgen Mahlknecht; Nirav P. Raval (Chemosphere, 2023)

The role of farming practice in nutrient assimilation in small-scale tilapia farming - Lara Parata; Joshua Noiney; Marwan E. Majzoub; Debashish Mazumder; Suhelen Egan; Jesmond Sammut (Aquaculture, 2023)

Impact of casein demineralization on the fouling of UHT plant and the heat stability of high protein beverages: A pilot scale study - Marwan Abdallah; Luisa Azevedo-Scudeller; Wenqian Sun; Amandine Descamps; Pierre Gourdin; Manon Hiolle; Alain Baniel; Céline Lesur; Guillaume Delaplace (Food and Bioproducts Processing, 2023)

Pollution characteristics and human health risk of potentially toxic elements associated with deposited dust of sporting walkways during physical activity - Mansour A. Alghamdi; Salwa K. Hassan; Marwan Y. Al Sharif; Mamdouh I. Khoder; Roy M. Harrison (Atmospheric Pollution Research, 2023)

An underground research laboratory at Château-Landon (France) to study the impact of climate change on the stability of abandoned mines - Nathalie Conil; Philippe Gombert; Marwan Al Heib; Nicolas Spitzenteder; Roxane Muller; Fabrice Gaumet; Danielle Pajiep (Bulletin of Engineering Geology and the Environment, 2023)

Fog type classification using a modified Richardson number for Christchurch, New Zealand - Dongqi Lin; Marwan Katurji; Laura E. Revell; Basit Khan; Neal Osborne; Iman Soltanzadeh; Stefanie Kremser (International Journal of Climatology, 2023)
Situated on a coastal plain between the Southern Alps and Banks Peninsula, Christchurch, New Zealand, experiences around 49 fog days every year. Given its complex topography, accurate fog forecasting is difficult at Christchurch International Airport (CHA). Climatological analysis of local fog events is an important first step to gain insight into the processes involved in the fog lifecycle. In this study, fog events were identified using 12 years of meteorological observations from an automatic weather station situated at CHA. A novel fog type classification method was developed using the modified Richardson number ( MRi ). The MRi fog type classification method assesses the local dynamic stability of a 1.25 m shallow layer of near‐surface air. Here, the MRi is used as a quantitative index to classify advection fog, advection–radiation fog, and radiation fog. Vertical gradients of air temperature and wind speed were derived for prefog and fog periods, and a number of criteria were applied to the MRi for the fog type classification. The fog type classification results were examined in correspondence with the derived fog intensity, duration, diurnal and seasonal variability of frequency of occurrences, and synoptic and local wind flows. In agreement with other fog studies across the world, fog occurs most frequently during local winter and spring. Radiation fog is the predominant type of fog identified at CHA, and its formation and development usually coincide with the local drainage northwesterlies. This study is the first to use long‐term observational data to investigate the fog climatology and typology at CHA in detail. The fog climatological characteristics presented in this study will serve as the basis of future fog studies in Christchurch. The presented MRi fog type classification method can potentially be used in fog characteristic studies worldwide.

The regulatory role of long non- coding RNAs as a novel controller of immune response against cancer cells - Dina Mofed; Jihad I Omran; Salwa Sabet; Ahmed A Baiomy; Marwan Emara; Tamer Z. Salem (Molecular Biology Reports, 2022)
Immunotherapy has been established as a promising therapy for different cancer types. However, many patients experience primary or secondary resistance to treatment. Immune cells and anti-inflammatory factors are regulated by long noncoding RNAs (lncRNAs). In addition, lncRNAs have a role in immune resistance through antigen presentation loss or attenuation, PD-L1 upregulation, loss of T-cell activities, and activation of G-MDSCs and Tregs in the tumor environment. LncRNAs can also influence the interaction between cancer stem cells and immune cells in the tumor microenvironment, potentially resulting in cancer stem cell resistance to immunotherapy. Immunological-related lncRNAs can influence immune responses either directly by affecting neighboring protein-coding genes or indirectly by sponging miRNAs through various mechanisms. We have emphasized the role and levels of expression of lncRNAs that have been linked to immune cell formation, differentiation, and activation, which may have an influence on immunotherapy efficacy.

A Review: The Antiviral Activity of Cyclic Peptides - Le Yi Chia; Palanirajan Vijayaraj Kumar; Marwan Abdelmahmoud Abdelkarim Maki; Guna Ravichandran; Sivasudha Thilagar (International Journal of Peptide Research and Therapeutics, 2022)

Correction to: Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)

Effect of partially hydrolyzed polyacrylamide (HPAM) on the bacterial communities of wetland rhizosphere soils and their efficiency in HPAM and alkane degradation - Raeid M. M. Abed; Marwan Al-Fori; Mahmood Al-Hinai; Jamal Al-Sabahi; Huda Al-Battashi; Stephane Prigent; Tom Headley (Environmental Science and Pollution Research, 2022)

Nutritional guidelines for the management of insulin resistance - Giovanna Muscogiuri; Luigi Barrea; Massimiliano Caprio; Florencia Ceriani; Alberto O. Chavez; Marwan El Ghoch; Evelyn Frias-Toral; Rucha J Mehta; Verna Mendez; Stavroula A. Paschou; Agnieszka Pazderska; Silvia Savastano; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Experimental study on the mitigation effects of deflection walls on debris flow hazards at the confluence of tributary and main river - Jiamei Wang; Marwan A. Hassan; Matteo Saletti; Xingguo Yang; Hongwei Zhou; Jiawen Zhou (Bulletin of Engineering Geology and the Environment, 2022)

Simulating wastewater treatment plants for heavy metals using machine learning models - Marwan Kheimi; Mohammad A. Almadani; Mohammad Zounemat-Kermani (Arabian Journal of Geosciences, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)
Purpose of Review Recognizing that in the context of global change, tree genetic diversity represents a crucial resource for future forest adaptation, we review and highlight the major forest genetics research achievements of the past decades in biodiversity-rich countries of the Mediterranean region. For this, we conducted a bibliometric analysis of the scientific literature spanning the past thirty years (1991–2020). Putting together the representative regionwide expertise of our co-authorship, we propose research perspectives for the next decade. Recent Findings Forest genetics research in Mediterranean countries is organized into three different scientific domains of unequal importance. The domain “Population diversity and Differentiation” related to over 62% of all publications of the period, the domain “Environmental conditions, growth and stress response” to almost 23%, and the domain “Phylogeography” to almost 15%. Citation rate was trending the opposite way, indicating a strong and sustained interest in phylogeography and a rising interest for genetics research related to climate change and drought resistance. The share of publications from Asia and Africa to the total within the Mediterranean increased significantly during the 30-year period analyzed, reaching just below 30% during the last decade. Summary Describing poorly known species and populations, including marginal populations, using the full potential of genomic methods, testing adaptation in common gardens, and modeling adaptive capacity to build reliable scenarios for forest management remain strategic research priorities. Delineating areas of high and low genetic diversity, for conservation and restoration, respectively, is needed. Joining forces between forest management and forest research, sharing data, experience, and knowledge within and among countries will have to progress significantly, e.g., to assess the potential of Mediterranean genetic resources as assisted migration material worldwide. Introductory quote: Let us collect with care the facts we can observe, let us consult experience wherever we can, and when this experience is inaccessible to us, let us assemble all the inductions which observation of facts analogous to those which escape us can furnish and let us assert nothing categorically; in this way, we shall be able little by little to discover the causes of a multitude of natural phenomena, and, perhaps, even of phenomena which seem the most incomprehensible... J.B. de Lamarck (Philosophie zoologique, 1809), cited by O. L anglet (1971).

A pilot survey for mapping the fault structure around the Geuredong volcano by using high-resolution global gravity - Muhammad Yanis; Marwan; Rinaldi Idroes; Nasrullah Zaini; Andri Yadi Paembonan; Riski Ananda; Azman Abdul Ghani (Acta Geophysica, 2022)

3D large-scale numerical model of open-pit lake slope stability—case study of Lake Most - Vincent Renaud; Marwan Al Heib; Jan Burda (Bulletin of Engineering Geology and the Environment, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Anomaly and cyber fraud detection in pipelines and supply chains for liquid fuels - Alinne Beteto; Vidal Melo; Jessica Lin; Marwan Alsultan; Eduardo Mario Dias; Elizabeth Korte; DeAndre A. Johnson; Negin Moghadasi; Thomas L. Polmateer; James H. Lambert (Environment Systems and Decisions, 2022)

Insights into Reaction Modeling and Product Characterization of Hazelnut Shell Pyrolysis - Marwan A. Mahmood; Selim Ceylan (BioEnergy Research, 2022)

Investigating the relevance of Environmental Kuznets curve hypothesis in Saudi Arabia: towards energy efficiency and minimal carbon dioxide emission - Marwan Abdullah Alsaedi; Faisal Abnisa; Peter Adeniyi Alaba; Hamisu Umar Farouk (Clean Technologies and Environmental Policy, 2022)

Undrained triaxial compression tests on three-dimensional reinforced sand: effect of the geocell height - Ismail Benessalah; Marwan Sadek; Pascal Villard; Ahmed Arab (European Journal of Environmental and Civil Engineering, 2022)

The evaluation of artificial talus implant on ankle joint contact characteristics: a finite element study based on four subjects - Tao Liu; Nadr Jomha; Samer Adeeb; Marwan El-Rich; Lindsey Westover (Medical & Biological Engineering & Computing, 2022)

Genome sequence of a multidrug-resistant Campylobacter coli strain isolated from a newborn with severe diarrhea in Lebanon - Fatima Bachir Halimeh; Rayane Rafei; Seydina M. Diene; Marwan Osman; Issmat I. Kassem; Randa Jamal Akoum; Walid Moudani; Monzer Hamze; Jean-Marc Rolain (Folia Microbiologica, 2022)

Numerical simulation of the force of infection and the typical times of SARS-CoV-2 disease for different location countries - Marwan Al-Raeei (Modeling Earth Systems and Environment, 2022)

Analysis of Faults' Effect on the Stability of Surface Lignite Mining Areas Using the Distinct Element Method - Marwan Al Heib; Ioannis E. Zevgolis; Alexandros I. Theocharis; Nikolaos C. Koukouzas; Stella Coccia (Geotechnical and Geological Engineering, 2022)

Bibliometric analysis of immigration and environmental degradation: evidence from past decades - Azyyati Anuar; Nur Fakhzan Marwan; John Smith; Sirinya Siriyanun; Arshian Sharif (Environmental Science and Pollution Research, 2022)

Historical, current, and emerging tools for identification and serotyping of Shigella - Fatima Bachir Halimeh; Rayane Rafei; Marwan Osman; Issmat I. Kassem; Seydina M. Diene; Fouad Dabboussi; Jean-Marc Rolain; Monzer Hamze (Brazilian Journal of Microbiology, 2021)

The water crisis and the conflict in the Middle East - Mohammed T. Bani Salameh; Marwan Alraggad; Sura T. Harahsheh (Sustainable Water Resources Management, 2021)

Watershed modelling development for generating runoff estimation of Sarida Catchment/Central West Bank - Marwan Ghanem; Muath Abu Sadah; Yacoub Keilani (Environmental Monitoring and Assessment, 2021)

Evaluation of the Pharmacologic Treatment of COVID-19 Pandemic in Iraq - Omeed Darweesh; Ghayth M. Abdulrazzaq; Radhwan N. Al-Zidan; Pshtiwan Bebane; Marwan Merkhan; Ruya Aldabbagh; Nohad AlOmari (Current Pharmacology Reports, 2021)

Space-time hydrochemical variations and water quality of Euphrates river - Bayan Muhie Hussien; Nabeel Fawzi Lattoofi; N. M. Abd-alghafour; Rasim Farraj Muslim; Tahseen Zaidan; Marwan Mahmood (Arabian Journal of Geosciences, 2021)

Adaptation of the Young Adults’ Cigarette Dependence (YACD) Scale for the development and validation of the Adolescent Cigarette Dependence Scale (ACDS) - Souheil Hallit; Sahar Obeid; Hala Sacre; Marwan Akel; Alessandro Khoury; Pascale Salameh (Environmental Science and Pollution Research, 2021)

Effect of Environmental Contaminants on Antioxidant Defense System in Fringe‐Lip Mullet (Crenimugil crenilabis) from Suez Canal, Egypt - Marwan A. Ibrahim; Rehab M. Mosaad (Bulletin of Environmental Contamination and Toxicology, 2021)

Correction to: Rationale and Design of a Telehealth Self-Management, Shared Care Intervention for Post-treatment Survivors of Lung and Colorectal Cancer - Virginia Sun; Anne Reb; Marc Debay; Marwan Fakih; Betty Ferrell (Journal of Cancer Education, 2021)
A Correction to this paper has been published: 10.1007/s13187-021-01969-5

Rationale and Design of a Telehealth Self-Management, Shared Care Intervention for Post-treatment Survivors of Lung and Colorectal Cancer - Virginia Sun; Anne Reb; Marc Debay; Marwan Fakih; Betty Ferrell (Journal of Cancer Education, 2021)
Survivors of lung and colorectal cancer have high post-treatment needs; the majority are older and suffer from greater comorbidities and poor quality of life (QOL). They remain underrepresented in research, leading to significant disparities in post-treatment outcomes. Personalized post-treatment follow-up care and care coordination among healthcare teams is a priority for survivors of lung and colorectal cancer. However, there are few evidence-based interventions that address survivors’ post-treatment needs beyond the use of a follow-up care plan. This paper describes the rationale and design of an evidence-informed telehealth intervention that integrates shared care coordination between oncology/primary care and self-management skills building to empower post-treatment survivors of lung and colorectal cancer. The intervention design was informed by (1) contemporary published evidence on cancer survivorship, (2) our previous research in lung and colorectal cancer survivorship, (3) the chronic care self-management model (CCM), and (4) shared post-treatment follow-up care between oncology and primary care. A two-arm, parallel randomized controlled trial will determine the efficacy of the telehealth intervention to improve cancer care delivery and survivor-specific outcomes. ClinicalTrials.gov Identifier: NCT04428905

Biallelic loss-of-function variants in NEMF cause central nervous system impairment and axonal polyneuropathy - Ashfaque Ahmed; Meng Wang; Gaber Bergant; Reza Maroofian; Rongjuan Zhao; Majid Alfadhel; Marwan Nashabat; Muhammad Talal AlRifai; Wafaa Eyaid; Abdulrahman Alswaid; Christian Beetz; Yan Qin; et al. (Human Genetics, 2021)

Cold plasma assisted deposition of organosilicon coatings on stainless steel for prevention of adhesion of Salmonella enterica serovar Enteritidis - Mayssane Hage; Simon Khelissa; Marwan Abdallah; Hikmat Akoum; Nour-Eddine Chihib; Charafeddine Jama (Biofouling, 2021)

Association of characters and temperaments with cigarette and waterpipe dependence among a sample of Lebanese adults - Emmanuelle Awad; Hala Sacre; Chadia Haddad; Marwan Akel; Pascale Salameh; Souheil Hallit; Sahar Obeid (Environmental Science and Pollution Research, 2021)

A frequency and velocity-dependent impedance method for prediction of rail/foundation dynamics - Reda Mezeh; Marwan Sadek; Fadi Hage Chehade; Isam Shahrour (Earthquake Engineering and Engineering Vibration, 2021)

Soil Densification Effect on the Behaviour of Chlef Sand (Algeria) under Static and Cyclic Loading: A Laboratory Investigation - Zohra Boutaraa; Ahmed Arab; Rachid Bouferra; Marwan Sadek (Geotechnical and Geological Engineering, 2020)

Update on invasive fungal infections in the Middle Eastern and North African region - Marwan Osman; Aisha Al Bikai; Rayane Rafei; Hassan Mallat; Fouad Dabboussi; Monzer Hamze (Brazilian Journal of Microbiology, 2020)

Analysis of four methods of measuring three-dimensional pelvic tilt in the lateral decubitus position - Meredith Stadnyk; Tao Liu; Fatemeh Fallahi Arezodar; Lindsey Westover; Jaime A. Carvajal Alba; Edward Masson; Lauren Beaupre; Jacob L. Jaremko; Marwan El-Rich (Medical & Biological Engineering & Computing, 2020)

Influence of soil–structure interaction on the fundamental frequency of shear wall structures - Marwan Sadek; Marwa Hussein; Fadi Hage Chehade; Ahmed Arab (Arabian Journal of Geosciences, 2020)

Therapeutic Aerosol: Thermodynamic Method for Managing the Aerosol Particle Size - Evgeny Olenev; Marwan A. A. Hamid; Walid Al-Haidri; E. A. Lebedinskaya (Aerosol Science and Engineering, 2020)

Atmospheric moisture pathways of East Africa and implications for water recycling at Mount Kilimanjaro - Benjamin Schumacher; Marwan Katurji; Hanna Meyer; Tim Appelhans; Insa Otte; Thomas Nauss (International Journal of Climatology, 2020)
The Mt. Kilimanjaro ecosystem depends on atmospheric moisture transport and recycling of water, yet limited knowledge on the relation between advective moisture pathways and local water recycling is available. This study uses a regional atmospheric model to analyse moisture source and sink processes as well as precipitation recycling at Mt. Kilimanjaro. The results indicate that locally produced precipitation is deposited mainly in June and July while trans‐regional effects are weak. Results also revealed the importance of tropical storm systems for local convection in the Kilimanjaro region and the effect of the Indian Ocean Zonal Mode phases on East African moisture pathways. The analysis further revealed connections between the Madagascar tip jet and the Turkana jet with implications for regional moisture pathways that have not been described before.

Comparing cigarette smoking knowledge and attitudes among smokers and non-smokers - Chadia Haddad; Hala Sacre; Aline Hajj; Nathalie Lahoud; Zeina Akiki; Marwan Akel; Danielle Saade; Rouba Karen Zeidan; Rita Farah; Souheil Hallit; Pascale Salameh (Environmental Science and Pollution Research, 2020)

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Knowledge, attitudes, harm perception, and practice related to waterpipe smoking in Lebanon - Chadia Haddad; Nathalie Lahoud; Marwan Akel; Hala Sacre; Aline Hajj; Souheil Hallit; Pascale Salameh (Environmental Science and Pollution Research, 2020)

Investigation and Classification of MRI Brain Tumors Using Feature Extraction Technique - Marwan A. A. Hamid; Najeed Ahmed Khan (Journal of Medical and Biological Engineering, 2020)

Neuroprotective effect of Crocus sativus against cerebral ischemia in rats - Rehab F. Abdel-Rahman; Sally A. El Awdan; Rehab R. Hegazy; Dina F. Mansour; H. A. Ogaly; Marwan Abdelbaset (Metabolic Brain Disease, 2020)

Study of the Effect of Thermal Dispersion on Internal Natural Convection in Porous Media Using Fourier Series - Marwan Fahs; Thomas Graf; Tuong Vi Tran; Behzad Ataie-Ashtiani; Craig. T. Simmons; Anis Younes (Transport in Porous Media, 2020)

Wavelet analysis of precipitation extremes over India and teleconnections to climate indices - Maheswaran Rathinasamy; Ankit Agarwal; Bellie Sivakumar; Norbert Marwan; Jürgen Kurths (Stochastic Environmental Research and Risk Assessment, 2019)

Myocardial regeneration: role of epicardium and implicated genes - Omran Saifi; Bachir Ghandour; Diana Jaalouk; Marwan Refaat; Rami Mahfouz (Molecular Biology Reports, 2019)

Investigation of spring water quality in the Natuv catchment, Palestine: a component for the regional environmental management system - Marwan Ghanem; Hassan Jebreen; Jon Sege; Yoram Rubin (Euro-Mediterranean Journal for Environmental Integration, 2019)

Locating suitable sites for the construction of underground dams using the subsurface flow simulation (SWAT model) and analytical network process (ANP) (case study: Daroongar watershed, Iran) - Ali Talebi; Ehsan Zahedi; Marwan A. Hassan; Mohammad Taghi Lesani (Sustainable Water Resources Management, 2019)

Classifying past climate change in the Chew Bahir basin, southern Ethiopia, using recurrence quantification analysis - Martin H. Trauth; Asfawossen Asrat; Walter Duesing; Verena Foerster; K. Hauke Kraemer; Norbert Marwan; Mark A. Maslin; Frank Schaebitz (Climate Dynamics, 2019)

Actively detached Pseudomonas aeruginosa biofilm cell susceptibility to benzalkonium chloride and associated resistance mechanism - Simon Oussama Khelissa; Marwan Abdallah; Charafeddine Jama; Nour-Eddine Chihib (Archives of Microbiology, 2019)

A network-based comparative study of extreme tropical and frontal storm rainfall over Japan - Ugur Ozturk; Nishant Malik; Kevin Cheung; Norbert Marwan; Juergen Kurths (Climate Dynamics, 2019)

Impact of growth temperature on the adhesion of colistin-resistant Escherichia coli strains isolated from pigs to food-contact-surfaces - Marwan Abdallah; Rabih Mourad; Simon Oussama khelissa; Charafeddine Jama; Medhat Abozid; Djamel Drider; Nour-Eddine Chihib (Archives of Microbiology, 2019)

Analytical model to predict building deflections induced by ground movements - Bakri Basmaji; Olivier Deck; Marwan Al Heib (European Journal of Environmental and Civil Engineering, 2019)

Experimental study on the liquefaction resistance of sand–clay mixtures: Effect of clay content and grading characteristics - Abdallh Krim; Ahmed Arab; Mohamed Chemam; Abdelkadr Brahim; Marwan Sadek; Isam Shahrour (Marine Georesources & Geotechnology, 2019)

Analysis of spatio‐temporal bias of Weather Research and Forecasting temperatures based on weather pattern classification - Renan Le Roux; Marwan Katurji; Peyman Zawar‐Reza; Hervé Quénol; Andrew Sturman (International Journal of Climatology, 2019)
Viticulture is a key economic activity for many countries around the world, and temperature is one of the most important parameters in grapevine response. Many studies have shown that variability of temperature at the vineyard scale has a significant effect on physiological development of the grapevine and, ultimately, wine quality. The Weather Research and Forecasting (WRF) model has been widely used to dynamically downscale from the synoptic and larger scale atmospheric circulation in order to provide a high‐resolution analysis of weather and climate in regions of complex terrain. The temperature bias of the WRF model in a vineyard region is analysed using 18 automatic weather stations in order to understand the spatial variation in the bias due to local conditions. The WRF‐predicted temperatures exhibited an average bias that was relatively consistent between measurement sites, although the consistency of this bias was found to vary in relation to weather type, time of day and season. These factors therefore need to be taken into account in order to properly correct temperatures produced by the WRF model.

The effect of hydraulic anisotropies on intensely exploited groundwater resources: the numerical evaluation of a hydrothermal transboundary aquifer system in the Middle East - Kalliopi Tzoufka; Fabien Magri; Tino Rödiger; Nimrod Inbar; Eyal Shalev; Peter Möller; Marwan Raggad; Eliyahu Rosenthal; Christian Siebert (Hydrogeology Journal, 2018)

Stimulation of ACE2/ANG(1–7)/Mas Axis by Diminazene Ameliorates Alzheimer’s Disease in the D-Galactose-Ovariectomized Rat Model: Role of PI3K/Akt Pathway - Ahmed S. Kamel; Noha F. Abdelkader; Sahar S. Abd El-Rahman; Marwan Emara; Hala F. Zaki; Mahmoud M. Khattab (Molecular Neurobiology, 2018)

Laboratory Investigation of the Influence of Geotextile on the Stress–Strain and Volumetric Change Behavior of Sand - Brahim Abdelkader; Ahmed Arab; Marwan Sadek; Isam Shahrour (Geotechnical and Geological Engineering, 2018)

Cantilever Contiguous Pile Wall for Supporting Excavation in Clay - Mohamed I. Ramadan; Ebraheem H. Ramadan; Marwan M. Khashila (Geotechnical and Geological Engineering, 2018)

Nonlinear interactions between the Amazon River basin and the Tropical North Atlantic at interannual timescales - Alejandro Builes-Jaramillo; Norbert Marwan; Germán Poveda; Jürgen Kurths (Climate Dynamics, 2018)

Recharge estimation in semi-arid karst catchments: Central West Bank, Palestine - Hassan Jebreen; Stefan Wohnlich; Frank Wisotzky; Andre Banning; Andrea Niedermayr; Marwan Ghanem (Grundwasser, 2018)

An Efficient ELLAM Implementation for Modeling Solute Transport in Fractured Porous Media - Fanilo Ramasomanana; Marwan Fahs; Husam Musa Baalousha; Nicolas Barth; Said Ahzi (Water, Air, & Soil Pollution, 2018)

Analytical solution and Bayesian inference for interference pumping tests in fractal dual-porosity media - Mohamed Hayek; Anis Younes; Jabran Zouali; Noura Fajraoui; Marwan Fahs (Computational Geosciences, 2018)

Assessing anthropogenic impacts on limited water resources under semi-arid conditions: three-dimensional transient regional modelling in Jordan - Tino Rödiger; Fabien Magri; Stefan Geyer; Shehan Tharaka Morandage; H. E. Ali Subah; Marwan Alraggad; Christian Siebert (Hydrogeology Journal, 2017)

Population structure and association mapping of traits related to reproductive development in field pea - Yunfei Jiang; Marwan Diapari; Rosalind A. Bueckert; Bunyamin Tar’an; Thomas D. Warkentin (Euphytica, 2017)

Mutation in SLC6A9 encoding a glycine transporter causes a novel form of non-ketotic hyperglycinemia in humans - Majid Alfadhel; Marwan Nashabat; Hanan Al Qahtani; Ahmed Alfares; Fuad Al Mutairi; Hesham Al Shaalan; Ganka V. Douglas; Klaas Wierenga; Jane Juusola; Muhammad Talal Alrifai; Stefan T. Arold; Fowzan Alkuraya; et al. (Human Genetics, 2016)

Detection of human pathogenic Fusarium species in hospital and communal sink biofilms by using a highly specific monoclonal antibody - Marwan Al‐Maqtoofi; Christopher R. Thornton (Environmental Microbiology, 2016)
Summary The fungus Fusarium is well known as a plant pathogen, but has recently emerged as an opportunistic pathogen of humans. Habitats providing direct human exposure to infectious propagules are largely unknown, but there is growing evidence that plumbing systems are sources of human pathogenic strains in the Fusarium solani species complex (FSSC) and Fusarium oxysporum species complex (FOSC), the most common groups infecting humans. Here, a newly developed Fusarium‐specific monoclonal antibody (mAb ED7) was used to track FSSC and FOSC strains in sink drain biofilms by detecting its target antigen, an extracellular 200 kDa carbohydrate, in saline swabs. The antigen was detectable in 52% of swab samples collected from sinks across a University campus and a tertiary care hospital. The mAb was 100% accurate in detecting FSSC, FOSC, and F. dimerum species complex (FDSC) strains that were present, as mixed fungal communities, in 83% of sink drain biofilms. Specificity of the ELISA was confirmed by sequencing of the internally transcribed spacer 1 (ITS1)‐5.8S‐ITS2 rRNA‐encoding regions of culturable yeasts and molds that were recovered using mycological culture, while translation elongation factor (TEF)‐1 α analysis of Fusarium isolates included FSSC 1‐a, FOSC 33, and FDSC ET‐gr, the most common clinical pathotypes in each group.

Fungal Mycotic Aneurysm of the Internal Carotid Artery Associated with Sphenoid Sinusitis in an Immunocompromised Patient: A Case Report and Review of the Literature - Marwan M. Azar; Roland Assi; Natalie Patel; Maricar F. Malinis (Mycopathologia, 2016)

Origin of high bromide concentration in the water sources in Jordan and in the Dead Sea water - Elias Salameh; Arwa Tarawneh; Marwan Al-Raggad (Arabian Journal of Geosciences, 2016)

Qualitative spring water management in the central western catchment of the West Bank from hydrochemical and environmental isotopes approaches - Marwan Ghanem; Hassan Jebreen; Jens Lange (Arabian Journal of Geosciences, 2016)

Exome-based case–control association study using extreme phenotype design reveals novel candidates with protective effect in diabetic retinopathy - Corina Shtir; Mohammed A. Aldahmesh; Saad Al-Dahmash; Emad Abboud; Hisham Alkuraya; Marwan A. Abouammoh; Sawsan R. Nowailaty; Ghazai Al-Thubaiti; E. A. Naim; B. ALYounes; F. S. Binhumaid; A. B. ALOtaibi; et al. (Human Genetics, 2016)

Saturation Effect on Behaviour of Sandy Soil Under Monotonic and Cyclic Loading: A Laboratory Investigation - A. Arab; M. Belkhatir; Marwan Sadek (Geotechnical and Geological Engineering, 2016)

Non-linear time series analysis of precipitation events using regional climate networks for Germany - Aljoscha Rheinwalt; Niklas Boers; Norbert Marwan; Jürgen Kurths; Peter Hoffmann; Friedrich-Wilhelm Gerstengarbe; Peter Werner (Climate Dynamics, 2016)

Spatiotemporal characteristics and synchronization of extreme rainfall in South America with focus on the Andes Mountain range - Niklas Boers; Bodo Bookhagen; Norbert Marwan; Jürgen Kurths (Climate Dynamics, 2016)

Extension of the Henry semi-analytical solution for saltwater intrusion in stratified domains - Anis Younes; Marwan Fahs (Computational Geosciences, 2015)

SNP variation within genes associated with amylose, total starch and crude protein concentration in field pea - Ambuj Bhushan Jha; Bunyamin Tar’an; Marwan Diapari; Thomas D. Warkentin (Euphytica, 2015)

How complex climate networks complement eigen techniques for the statistical analysis of climatological data - Jonathan F. Donges; Irina Petrova; Alexander Loew; Norbert Marwan; Jürgen Kurths (Climate Dynamics, 2015)

The confusion assessment method for the intensive care unit in patients with cirrhosis - Eric S. Orman; Anthony Perkins; Marwan Ghabril; Babar A. Khan; Naga Chalasani; Malaz A. Boustani (Metabolic Brain Disease, 2015)

Analysis of the historical collapse of an abandoned underground chalk mine in 1961 in Clamart (Paris, France) - Marwan Al Heib; Christophe Duval; Fiona Theoleyre; Jean-Marc Watelet; Philippe Gombert (Bulletin of Engineering Geology and the Environment, 2015)

Association of systemic inflammation with epicardial fat and coronary artery calcification - Sören Gauss; Lutz Klinghammer; Alina Steinhoff; Dorette Raaz-Schrauder; Mohamed Marwan; Stephan Achenbach; Christoph D. Garlichs (Inflammation Research, 2015)

Allele diversity analysis to identify SNPs associated with ascochyta blight resistance in pea - Ambuj Bhushan Jha; Bunyamin Tar’an; Marwan Diapari; Anoop Sindhu; Arun Shunmugam; Kirstin Bett; Thomas D. Warkentin (Euphytica, 2015)

Role des effondrements karstiques sur les desordres survenus sur les digues de Loire dans le Val D’Orleans (France) - Philippe Gombert; Julie Orsat; David Mathon; Rafid Alboresha; Marwan Al Heib; Olivier Deck (Bulletin of Engineering Geology and the Environment, 2015)

Effect of culture conditions on the resistance of Pseudomonas aeruginosa biofilms to disinfecting agents - Marwan Abdallah; Corinne Benoliel; Pauline Ferreira-Theret; Djamel Drider; Pascal Dhulster; Nour-Eddine Chihib (Biofouling, 2015)

Gene-based SNP discovery and genetic mapping in pea - Anoop Sindhu; Larissa Ramsay; Lacey-Anne Sanderson; Robert Stonehouse; Rong Li; Janet Condie; Arun S. K. Shunmugam; Yong Liu; Ambuj B. Jha; Marwan Diapari; Judith Burstin; Gregoire Aubert; et al. (Theoretical and Applied Genetics, 2014)

Antifouling properties of zinc oxide nanorod coatings - Marwan Al-Fori; Sergey Dobretsov; Myo Tay Zar Myint; Joydeep Dutta (Biofouling, 2014)

Biofilm formation and persistence on abiotic surfaces in the context of food and medical environments - Marwan Abdallah; Corinne Benoliel; Djamel Drider; Pascal Dhulster; Nour-Eddine Chihib (Archives of Microbiology, 2014)

Groundwater recharge zones mapping using GIS: a case study in Southern part of Jordan Valley, Jordan - Nezar Hammouri; Hani Al-Amoush; Marwan Al-Raggad; Sura Harahsheh (Arabian Journal of Geosciences, 2014)

Accuracy assessment of land surface temperature retrievals from Landsat 7 ETM + in the Dry Valleys of Antarctica using iButton temperature loggers and weather station data - Lars Brabyn; Peyman Zawar-Reza; Glen Stichbury; Craig Cary; Bryan Storey; Daniel C. Laughlin; Marwan Katurji (Environmental Monitoring and Assessment, 2014)

Characterization and concentrations of polycyclic aromatic hydrocarbons in emissions from different heating systems in Damascus, Syria - Farouk Alkurdi; François Karabet; Marwan Dimashki (Environmental Science and Pollution Research, 2014)

A semi-analytical solution for saltwater intrusion with a very narrow transition zone - Anis Younes; Marwan Fahs (Hydrogeology Journal, 2014)

Generalization of the MAFRAM Methodology for Semi-Volatile Organic Agro-Chemicals - Mohammad A. Batiha; Leema A. Al-Makhadmeh; Marwan M. Batiha; Ashraf Ramadan; Abdul Amir H. Kadhum (Water, Air, & Soil Pollution, 2014)

A Semi-Analytical Solution for the Reactive Henry Saltwater Intrusion Problem - Anis Younes; Marwan Fahs (Water, Air, & Soil Pollution, 2013)

mTOR and regulation of energy homeostasis in humans - Marwan Mannaa; Stephanie Krämer; Michael Boschmann; Maik Gollasch (Journal of Molecular Medicine, 2013)

Changes in Membrane Fatty Acid Composition of Pseudomonas aeruginosa in Response to UV-C Radiations - Salma Kloula Ben Ghorbal; Abdelwaheb Chatti; Mohamed Marwan Sethom; Lobna Maalej; Mouadh Mihoub; Sana Kefacha; Moncef Feki; Ahmed Landoulsi; Abdennaceur Hassen (Current Microbiology, 2013)

Late Holocene Asian summer monsoon dynamics from small but complex networks of paleoclimate data - Kira Rehfeld; Norbert Marwan; Sebastian F. M. Breitenbach; Jürgen Kurths (Climate Dynamics, 2013)

Levels of Heavy Metals and Essential Minerals in Hair Samples of Children with Autism in Oman: a Case–Control Study - Yahya M. Al-Farsi; Mostafa I. Waly; Marwan M. Al-Sharbati; Mohammed A. Al-Shafaee; Omar A. Al-Farsi; Maha M. Al-Khaduri; Ishita Gupta; Allal Ouhtit; Samir Al-Adawi; Mona F. Al-Said; Richard C. Deth (Biological Trace Element Research, 2013)

Improved pig donor screening including newly identified variants of porcine endogenous retrovirus-C (PERV-C) - Danny Kaulitz; Debora Mihica; Cornelia Adlhoch; Marwan Semaan; Joachim Denner (Archives of Virology, 2013)

Experimental analysis of the influence of crumb rubber addition on the short-term aging of Syrian asphalt - Bassem Ali; Marwan Sadek (Arabian Journal of Geosciences, 2013)

Analysis of spatial and temporal extreme monsoonal rainfall over South Asia using complex networks - Nishant Malik; Bodo Bookhagen; Norbert Marwan; Jürgen Kurths (Climate Dynamics, 2012)

Application of carbon nanotubes in neurology: clinical perspectives and toxicological risks - Antonio Nunes; Khuloud Al-Jamal; Takeshi Nakajima; Marwan Hariz; Kostas Kostarelos (Archives of Toxicology, 2012)

Increased Markers of Oxidative Stress in Autistic Children of the Sultanate of Oman - Musthafa M. Essa; Gilles J. Guillemin; Mostafa I. Waly; Marwan M. Al-Sharbati; Yahya M. Al-Farsi; Faruck L. Hakkim; Amanat Ali; Mohammed S. Al-Shafaee (Biological Trace Element Research, 2012)

An Investigation into Ridge-Top Turbulence Characteristics During Neutral and Weakly Stable Conditions: Velocity Spectra and Isotropy - Marwan Katurji; Andrew Sturman; Peyman Zawar-Reza (Boundary-Layer Meteorology, 2011)

An Efficient Implementation of the Method of Lines for Multicomponent Reactive Transport Equations - Marwan Fahs; Anis Younes; Philippe Ackerer (Water, Air, & Soil Pollution, 2011)

A lake sediment-based proxy of floods in the Rocky Mountain Front Ranges, Canada - Erik Schiefer; Robert Gilbert; Marwan A. Hassan (Journal of Paleolimnology, 2011)

Erratum to: Improving Short- and Long-term Stability of Underground Gypsum Mine Using Partial and Total Backfill - Mohamed Marwan Al Heib; Christophe Didier; Farimah Masrouri (Rock Mechanics and Rock Engineering, 2010)

Improving Short- and Long-term Stability of Underground Gypsum Mine Using Partial and Total Backfill - Mohamed Marwan Al Heib; Christophe Didier; Farimeh Masrouri (Rock Mechanics and Rock Engineering, 2010)

Histomorphometric evaluation of cannabinoid receptor and anandamide modulating enzyme expression in the human endometrium through the menstrual cycle - Anthony H. Taylor; Muna S. Abbas; Marwan A. Habiba; Justin C. Konje (Histochemistry and Cell Biology, 2010)

Effect of bitter vetch (Vicia ervilia) seeds as a replacement protein source of soybean meal on performance and carcass characteristics of finishing Awassi lambs - Abdullah Y. Abdullah; Marwan M. Muwalla; Rasha I. Qudsieh; Hosam H. Titi (Tropical Animal Health and Production, 2010)

Method for patient-specific finite element modeling and simulation of deep brain stimulation - Mattias Åström; Ludvic U. Zrinzo; Stephen Tisch; Elina Tripoliti; Marwan I. Hariz; Karin Wårdell (Medical & Biological Engineering & Computing, 2009)

On the Efficiency of the Direct Substitution Approach for Reactive Transport Problems in Porous Media - Marwan Fahs; Jérôme Carrayrou; Anis Younes; Philippe Ackerer (Water, Air, & Soil Pollution, 2008)

The Sun Health Research Institute Brain Donation Program: Description and Eexperience, 1987–2007 - Thomas G. Beach; Lucia I. Sue; Douglas G. Walker; Alex E. Roher; LihFen Lue; Linda Vedders; Donald J. Connor; Marwan N. Sabbagh; Joseph Rogers (Cell and Tissue Banking, 2008)

The Sun Health Research Institute Brain Donation Program: description and experience, 1987–2007 - Thomas G. Beach; Lucia I. Sue; Douglas G. Walker; Alex E. Roher; LihFen Lue; Linda Vedders; Donald J. Connor; Marwan N. Sabbagh; Joseph Rogers (Cell and Tissue Banking, 2007)

Order patterns recurrence plots in the analysis of ERP data - Stefan Schinkel; Norbert Marwan; Jürgen Kurths (Cognitive Neurodynamics, 2007)

Phenylalkylamine alkaloids from Stapelia hirsuta L. - Marwan Shabana; Mariam Gonaid; Maha Mahmoud Salama; Essam Abdel-Sattar (Natural Product Research, 2006)

Molecular mechanisms of metastasis - Dave S. B. Hoon; Minoru Kitago; Joseph Kim; Takuji Mori; Adriano Piris; Katherine Szyfelbein; Martin C. Mihm; S. David Nathanson; Timothy P. Padera; Ann F. Chambers; Sharon A. Vantyghem; Ian C. MacDonald; et al. (Cancer and Metastasis Reviews, 2006)

Developmental expression patterns and regulation of connexins in the mouse mammary gland: expression of connexin30 in lactogenesis - Rabih S. Talhouk; Randolph C. Elble; Rola Bassam; Mariam Daher; Agnel Sfeir; Lina Abi Mosleh; Hilda El-Khoury; Samar Hamoui; Bendicht U. Pauli; Marwan E. El-Sabban (Cell and Tissue Research, 2005)

Comparing modern and Pleistocene ENSO-like influences in NW Argentina using nonlinear time series analysis methods - N. Marwan; M. H. Trauth; M. Vuille; J. Kurths (Climate Dynamics, 2003)

Impacts of Irrigation with Water Containing Heavy Metals on Soil and Groundwater – A Simulation Study - Mohammed M. Al-Subu; Marwan Haddad; Numan Mizyed; Inaya Mizyed (Water, Air, & Soil Pollution, 2003)

Should the guidelines for monitoring serum cholesterol levels in the elderly be re-evaluated? - D. Larry Sparks; Donald J. Connor; Patrick Browne; Marwan N. Sabbagh (Journal of Molecular Neuroscience, 2002)

Minimally Invasive Estimation of Systemic Vascular Parameters - Yih-Choung Yu; J. Robert Boston; Marwan A. Simaan; James F. Antaki (Annals of Biomedical Engineering, 2001)

β1-integrin-mediated dynamic adhesion of colon carcinoma cells to extracellular matrix under laminar flow - Jörg Haier; Marwan Y. Nasralla; Garth L. Nicolson (Clinical & Experimental Metastasis, 1999)

An Evaluation of Public Concerns About Water Management in the Palestinian Territory Pre, During, and Post the National Uprising - Marwan Haddad; Aidah Bakir (Water Resources Management, 1998)

Effects of iron, zinc, calcium, and vitamins on the activity and contents of human placental copper/zinc and manganese superoxide dismutases - Abdelrahim A. Hunaiti; Marwan S. Saleh (Biological Trace Element Research, 1996)